Chemically strengthened microcrystalline glass, cover plate glass, electronic equipment and glass device
By adjusting the stress characteristics and component content in chemically strengthened microcrystalline glass, the problem of inappropriate stress distribution during the reinforcement process of lithium-content microcrystalline glass is solved, and its double improvement in damage resistance and safety performance is achieved.
Patent Information
- Application Number
- CN202411386934.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-30
AI Technical Summary
During the chemical strengthening process of lithium disilicate microcrystalline glass with high lithium content, the increase in overall stress level does not necessarily ensure that it has excellent damage resistance, and it is prone to inappropriate stress distribution, resulting in a decrease in strengthening stability. There are even safety hazards of explosive cracking.
By enabling chemically strengthened microcrystalline glass to meet specific stress characteristics and have a specific stress distribution structure, ensuring that it maintains a safe stress state while improving mechanical strength and damage resistance. Specific measures include adjusting the mass percentage of the lithium disilicate crystal phase, controlling the depth and distribution of the compressive stress layer and the tensile stress layer, and optimizing the surface component content.
It has achieved chemically strengthened microcrystalline glass with excellent anti-damage performance and high safety performance. It produces large fragments when it is broken by falling impact, and does not form a large number of fine fragments, avoids safety hazards, and meets emergency use needs after breaking.
Smart Images

Figure CN119409417A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of microcrystalline glass, and in particular to a chemically strengthened microcrystalline glass, a cover glass, an electronic device and a glass device. Background Art
[0002] Lithium disilicate glass-ceramics is a type of glass-ceramics with lithium disilicate as the main crystalline phase. Inside the glass-ceramics, lithium disilicate crystals are randomly oriented and interlocked microstructures, forcing the crack path to be distorted when passing through the crystal, thereby preventing the crack from expanding and improving the strength and fracture toughness of the glass-ceramics. In addition, the optical refractive index of lithium disilicate crystals is close to that of the glass matrix, making it an ideal crystalline phase for preparing highly transparent glass-ceramics. Therefore, lithium disilicate glass-ceramics has great application potential in the cover market for electronic devices.
[0003] With the continuous development of the industry, the demand for ultra-thin design of electronic devices has become increasingly prominent, and it is also expected that the glass used as cover glass in electronic devices (such as mobile phones, watches, PADs, etc.) is as thin as possible. Therefore, in order to meet the use requirements of electronic devices, such as meeting high performance requirements such as anti-fall, pressure resistance, scratch resistance, and wear resistance, it is usually necessary to chemically strengthen the glass used as cover glass to prepare a strengthened microcrystalline glass with a certain stress level. The obtained stress level combined with its own inherent strength can play a resistance role when the strengthened microcrystalline glass is subjected to external forces, thereby preventing the strengthened microcrystalline glass from being damaged, so as to further improve its anti-destruction performance. Superior anti-destruction performance often requires the cover glass to have a high stress level. Summary of the invention
[0004] Without being limited by any theory, the inventors have found that for lithium disilicate glass-ceramics with a high lithium content, the improvement of the overall stress level does not necessarily ensure that it obtains excellent damage resistance. If during strengthening, only the improvement of the overall stress level is paid attention to, and the stress distribution is not paid attention to, it is often easy to have inappropriate stress distribution in the obtained chemically strengthened glass-ceramics, resulting in the phenomenon of "reduced strengthening stability". When the overall stress level is increased, the tensile stress in a certain area inside is too large. Such a stress distribution structure not only cannot ensure that the chemically strengthened glass-ceramics achieves excellent damage resistance, but also brings safety hazards, causing the chemically strengthened glass-ceramics to be prone to explosive cracking under slight impact, small fragments to fly everywhere, and even prone to self-explosion, which will seriously affect the reliability of chemically strengthened glass-ceramics products and have a serious impact on the personal safety of users.
[0005] In view of this, for microcrystalline glass with lithium disilicate as the main crystalline phase, the present application makes the chemically strengthened microcrystalline glass meet specific stress characteristics and has a specific stress distribution structure. While ensuring the improvement of the mechanical strength performance of the chemically strengthened microcrystalline glass and improving its damage resistance, the chemically strengthened microcrystalline glass maintains a safe stress state and has higher safety performance.
[0006] The present application provides a chemically strengthened glass-ceramic and a cover glass, electronic device and glass device containing the chemically strengthened glass-ceramic. The chemically strengthened glass-ceramic satisfies a specific crystal phase structure and stress distribution structure, so that the chemically strengthened glass-ceramic has both excellent damage resistance (such as excellent resistance to drop damage) and high safety performance. The "high safety performance" here is mainly reflected in: when the chemically strengthened glass-ceramic is broken by falling and impact, the fragments produced are relatively large, and a large number of small fragments that are easy to splash around will not be formed, which can avoid safety hazards. When the chemically strengthened glass-ceramic is used as the cover glass of a display screen, it can also meet emergency use needs after falling and breaking.
[0007] Specifically, the technical solutions provided by this application include:
[0008] In a first aspect, a chemically strengthened glass-ceramic is provided, wherein the chemically strengthened glass-ceramic contains a lithium disilicate crystalline phase, wherein the lithium disilicate crystalline phase has a higher mass percentage than other crystalline phases present in the chemically strengthened glass-ceramic;
[0009] The chemically strengthened glass-ceramics has a compressive stress layer on the surface and a tensile stress layer inside;
[0010] The chemically strengthened glass-ceramics satisfies the following relationship:
[0011] A ≥ 49500, preferably A ≥ 50000, more preferably A ≥ 51000, more preferably the value of A is 49500 to 65000;
[0012] Wherein, CT_LD is the tensile stress linear density, in MPa / mm, CT_LD≥60000MPa / mm,
[0013] t is the thickness of chemically strengthened glass-ceramics, in mm,
[0014] is the ratio of the stress integral of the tensile stress layer from 2 times DOL_0 from the main surface of the chemically strengthened glass-ceramics to the position half the thickness of the chemically strengthened glass-ceramics along the thickness direction of the chemically strengthened glass-ceramics to the thickness t, in units of MPa / mm, where x is the depth from the main surface of the chemically strengthened glass-ceramics,
[0015] In relational formula A, the data is substituted into the calculation according to the above-mentioned unit requirements, and the calculation results are obtained. The units do not participate in the calculation. The A value represents the tensile stress line density (in the present application, the tensile stress line density value is basically approximately the ratio of the definite integral of the tensile stress curve to the thickness of the chemically strengthened microcrystalline glass) minus the ratio of the stress integral of the tensile stress layer from 2 times DOL_0 from the main surface of the chemically strengthened microcrystalline glass to half the thickness of the chemically strengthened microcrystalline glass to the thickness t.
[0016] The present application satisfies a specific stress distribution structure by making the tensile stress line density value of the chemically strengthened microcrystalline glass whose main crystal phase is the lithium disilicate crystal phase and the ratio of the stress integral of the tensile stress layer near the middle position to the thickness t satisfy a specific difference relationship. While ensuring that the chemically strengthened microcrystalline glass has a higher overall stress level, the internal stress distribution of the chemically strengthened microcrystalline glass can be guaranteed to be safer, thereby facilitating the chemically strengthened microcrystalline glass to maintain a safe stress state. The chemically strengthened microcrystalline glass of the present application can not only achieve excellent damage resistance, such as excellent resistance to drop damage, but also has high safety performance. When it encounters impact and breakage, the fragments generated are relatively large, and a large number of small fragments that are easy to splash around will not be formed, which can avoid safety hazards and meet emergency use needs after breaking.
[0017] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies the following relationship:
[0018] B=[|CT_AV|×(t / 2-DOL_0)]×[5×M K2O / (5×M K2O +0.5×M Na2O )], B ≥ 9000MPa·μm,
[0019] Preferably, B ≥ 9100 MPa·μm, more preferably, B ≥ 9200 MPa·μm, more preferably, the value of B is 9000 MPa·μm to 13000 MPa·μm;
[0020] Where |CT_AV| is the absolute value of the average tensile stress,
[0021] t is the thickness of chemically strengthened glass-ceramics,
[0022] M K2O is the mass percentage of K2O on the surface of chemically strengthened glass-ceramics,
[0023] M Na2O is the mass percentage of Na2O on the surface of chemically strengthened glass-ceramics.
[0024] The present application enables the chemically strengthened microcrystalline glass to have an optimal stress level by ensuring that the chemically strengthened microcrystalline glass has good single-rod static pressure resistance and high hardness by satisfying a specific relationship between the stress characteristics and the surface component content of the chemically strengthened microcrystalline glass.
[0025] In some embodiments of the present application, the value of relational formula A is: 54802.89, 51024.81, 57170.35, 52689.22, 52272.54, 58526.63, 54807.04, 56429.32, 52815.28, 53580.63, 54032.42, 54060.10, 53361.40 or 54841.31.
[0026] In some embodiments of the present application, the value of relational formula B is: 10333.74 MPa·μm, 11642.77 MPa·μm, 11864.03 MPa·μm, 10818.69 MPa·μm, 10199.45 MPa·μm, 10638.55 MPa·μm, 10862.45 MPa·μm, 9442.20 MPa·μm, 9292.34 MPa·μm, 10157.90 MPa·μm, 10637.99 MPa·μm, 10907.18 MPa·μm, 10429.05 MPa·μm or 11586.62 MPa·μm.
[0027] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies the following relationship: C=CS_50 / |CT_CV|, C≥0.85, preferably 0.85-1.5, more preferably 0.9-1.3, more preferably 0.9-1.2; wherein CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened glass-ceramics, in MPa, and |CT_CV| is the absolute value of the maximum tensile stress, in MPa. The present application facilitates the chemically strengthened glass-ceramics to have a better stress level by satisfying a specific relationship between the stress characteristics of the chemically strengthened glass-ceramics, thereby facilitating the realization that even after being broken, its fragments are relatively large, and a large number of small fragments that are easy to splash around will not be formed, which is conducive to avoiding safety hazards. When the chemically strengthened glass-ceramics is used as the cover glass of a display screen, it can also meet emergency use requirements after falling and breaking.
[0028] In some embodiments of the present application, the value of the relationship C is: 0.93, 1.12, 1.00, 0.97, 1.03, 0.99, 1.01, 0.98, 0.92, 1.05 or 1.06.
[0029] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies:
[0030] 140.00 MPa≤CS_50, preferably, 180.00 MPa≤CS_50, more preferably, 180.00 MPa≤CS_50≤240.00 MPa, wherein CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened microcrystalline glass; and / or,
[0031] 90.00 μm≤DOL_0, preferably, 100.00 μm≤DOL_0, more preferably, 100.00 μm≤DOL_0≤160.00 μm, wherein DOL_0 is the depth of the compressive stress layer; and / or,
[0032] 0.18≤DOL_0 / t, preferably, 0.20≤DOL_0 / t≤0.25, more preferably, 0.22≤DOL_0 / t≤0.23, wherein DOL_0 is the depth of the compressive stress layer, and t is the thickness of the chemically strengthened glass-ceramics; and / or,
[0033] 150MPa≤|CT_CV|, preferably, 150MPa≤|CT_CV|≤250MPa, more preferably, 180MPa≤|CT_CV|≤250MPa, wherein |CT_CV| is the absolute value of the maximum tensile stress; and / or,
[0034] 100.00 MPa≤|CT_AV|, preferably, 100.00 MPa≤|CT_AV|≤160.00 MPa, more preferably, 130.00 MPa≤|CT_AV|≤160.00 MPa, wherein |CT_AV| is the absolute value of the average tensile stress; and / or,
[0035] 65000.00MPa / mm≤CT_LD≤90000.00MPa / mm, more preferably, 70000.00MPa / mm≤CT_LD≤90000.00MPa / mm, wherein CT_LD refers to tensile stress linear density; and / or,
[0036] M K2O ≤3.0%, preferably 0.2% to 2%, more preferably 0.3% to 1.6%, wherein M K2O is the mass percentage of K2O on the surface of chemically strengthened glass-ceramics; and / or,
[0037] M Na2O ≥5.0%, preferably 5.0% to 20%, more preferably 6% to 17%, wherein M Na2Ois the mass percentage of Na2O on the surface of chemically strengthened microcrystalline glass. The present application facilitates obtaining chemically strengthened microcrystalline glass products with high stress levels by making the chemically strengthened microcrystalline glass meet appropriate stress characteristics and / or surface composition characteristics, thereby facilitating the improvement of mechanical strength performance by stress characteristics, and making the chemically strengthened microcrystalline glass meet excellent damage resistance and high safety performance.
[0038] In some embodiments of the present application, after the two main surfaces of the chemically strengthened micro-ceramic glass are thinned by 3 μm, the chemical micro-ceramic glass obtained satisfies: the mass percentage M' of K2O on the surface of the chemical micro-ceramic glass K2O and the mass percentage of Na2O on the surface of chemical glass-ceramics M' Na2O for:
[0039] M' K2O <3.0%, preferably 0.0% to 1%, more preferably 0.1% to 0.5%,
[0040] M' Na2O <15.0%, preferably 3.0% to 14%, more preferably 4% to 12%.
[0041] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies:
[0042] CS_50 is 210.89 MPa, 216.96 MPa, 216.18 MPa, 217.56 MPa, 216.54 MPa, 214.69 MPa, 217.72 MPa, 218.14 MPa, 216.14 MPa, 212.31 MPa, 213.77 MPa, 215.64 MPa, 201.79 MPa or 213.58 MPa, where CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened microcrystalline glass.
[0043] In some embodiments of the present application, DOL_0 is 110.04 μm, 107.70 μm, 109.97 μm, 109.32 μm, 109.13 μm, 109.87 μm, 109.42 μm, 110.63 μm, 109.11 μm, 108.94 μm, 111.27 μm, 106.65 μm or 119.97 μm, wherein DOL_0 is the depth of the compressive stress layer.
[0044] In some embodiments of the present application, DOL_0 / t is 0.18, 0.19, 0.20, 0.21, 0.24, 0.25, 0.22 or 0.23, wherein DOL_0 is the depth of the compressive stress layer and t is the thickness of the chemically strengthened glass-ceramics.
[0045] In some embodiments of the present application, |CT_CV| is 226.68 MPa, 193.35 MPa, 215.52 MPa, 224.35 MPa, 209.26 MPa, 217.21 MPa, 216.52 MPa, 222.24 MPa, 234.28 MPa, 202.79 MPa, 201.74 MPa, 218.25 MPa, 219.42 MPa or 207.75 MPa, wherein |CT_CV| is the absolute value of the maximum tensile stress of the chemically strengthened glass-ceramics.
[0046] In some embodiments of the present application, |CT_AV| is 145.28 MPa, 135.44 MPa, 147.26 MPa, 142.53 MPa, 138.79 MPa, 150.24 MPa, 144.35 MPa, 146.02 MPa, 142.02 MPa, 139.69 MPa, 140.56 MPa, 139.63 MPa, 142.25 MPa or 138.91 MPa, wherein |CT_AV| is the absolute value of the average tensile stress.
[0047] In some embodiments of the present application, CT_LD is 81333.56MPa / mm, 77092.45MPa / mm, 82483.27MPa / mm, 80204.48MPa / mm, 78205.39MPa / mm, 84212.52MPa / mm, 81170.89MPa / mm, 81403.23MPa / mm, 79173.31MPa / mm, 78723.70MPa / mm, 79309.57MPa / mm, 77483.48MPa / mm, 77692.71MPa / mm or 72249.87MPa / mm, wherein CT_LD refers to the tensile stress linear density.
[0048] In some embodiments of the present application, M Na2O is 12.87%, 7.93%, 10.85%, 12.63%, 13.02%, 13.63%, 15.25%, 16.16%, 12.75%, 12.18%, 11.95%, 11.26% or 12.14%, among which M Na2O is the mass percentage of Na2O on the surface of chemically strengthened glass-ceramics.
[0049] In some embodiments of the present application, M K2O 1.33%, 1.21%, 1.47%, 1.48%, 1.42%, 1.57%, 1.32%, 1.43%, 1.36%, 1.41%, 1.54%, 1.5% or 1.52%, among which MK2O is the mass percentage of K2O on the surface of chemically strengthened glass-ceramics.
[0050] In some embodiments of the present application, M' K2O is 0.300%, 0.289%, 0.318%, 0.321%, 0.315%, 0.301%, 0.326%, 0.305%, 0.322%, 0.319% or 0.325%, wherein M' K2O It is the mass percentage of K2O on the surface of the chemically strengthened microcrystalline glass after thinning the two main surfaces of the chemically strengthened microcrystalline glass by 3μm along the thickness direction.
[0051] In some embodiments of the present application, M' Na2O is 8.40%, 5.03%, 6.78%, 8.31%, 8.86%, 8.81%, 9.02%, 9.55%, 9.71%, 8.36%, 8.07%, 8.01%, 7.83% or 8.08%, wherein M' Na2O It is the mass percentage of Na2O on the surface of the chemically strengthened microcrystalline glass after thinning the two main surfaces of the chemically strengthened microcrystalline glass by 3μm along the thickness direction.
[0052] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in mole percentage of oxides, comprises:
[0053] SiO2: 58% to 66%, Al2O3: 0% to 3.5%, P2O5: 1% to 2.5%, ZrO2: 3.5% to 5.5%, Li2O: 22% to 32%, SrO: 0% to 2.5%, Na2O: 0% to 3%. In the present application, by adjusting and controlling the content range of each oxide component, it is beneficial to ensure that the chemically strengthened microcrystalline glass that meets the desired crystal phase structure and stress structure is obtained.
[0054] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in molar percentage of oxides, further comprises:
[0055] K2O: 0% to 1%, CaO: 0% to 1.5%, B2O3: 0% to 1%, Ta2O5: 0% to 1%, BaO: 0% to 2.5%.
[0056] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in mole percentage of oxides, comprises:
[0057] The molar percentage of SiO2 is 60% to 65%, preferably 60.5% to 64.50%; and / or,
[0058] The molar percentage of Al2O3 is 1% to 3.5%, preferably 1.00% to 2.5%, more preferably 1% to 1.5%; and / or,
[0059] The molar percentage of P2O5 is 1.00% to 2%, preferably 1.20% to 2%; and / or,
[0060] The molar percentage of ZrO2 is 4% to 5%, preferably 4.20% to 5%; and / or,
[0061] The molar percentage of Li2O is 23% to 31%, preferably 24% to 30%, more preferably 27% to 30%; and / or,
[0062] The molar percentage of SrO is 0% to 2%, preferably 0% to 1.9%; and / or,
[0063] The molar percentage of Na2O is 0% to 2.6%, preferably 0% to 1%; and / or,
[0064] The molar percentage of K2O is 0% to 0.7%, preferably 0% to 0.5%; and / or,
[0065] The molar percentage of CaO is 0% to 1%, preferably 0% to 0.95%; and / or,
[0066] The molar percentage of B2O3 is 0% to 0.7%, preferably 0% to 0.5%; and / or,
[0067] The molar percentage of Ta2O5 is 0% to 0.7%, preferably 0% to 0.5%; and / or,
[0068] The molar percentage of BaO is 0% to 2%, preferably 0% to 1.9%.
[0069] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in mole percentage of oxides, comprises:
[0070] SiO2 is 60.94%, 61.15%, 61.22%, 61.43%, 61.72% or 62.22%; and / or,
[0071] Al2O3 is 1.22%, 1.37%, 1.38% or 1.4%; and / or,
[0072] P2O5 is 1.82%, 1.83%, 1.84%, 1.85% or 1.86%; and / or,
[0073] ZrO2 is 4.47%, 4.57%, 4.59%, 4.6%, 4.61% or 4.66%; and / or,
[0074] Li2O is 29.25%, 29.38%, 29.39%, 29.4% or 29.52%; and / or,
[0075] SrO is 0%, 1.38% or 1.83%; and / or,
[0076] Na2O is 0% or 0.46%; and / or,
[0077] K2O is 0% or 0.46%; and / or,
[0078] CaO is 0% or 0.92%; and / or,
[0079] B2O3 is 0%, 0.2% or 0.46%; and / or,
[0080] Ta2O5 is 0% or 0.46%; and / or,
[0081] BaO is 0%, 1.37%, 1.38% or 1.83%.
[0082] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies:
[0083] 2.00≤n(SiO2) / n(Li2O)≤2.40, preferably, 2.00≤n(SiO2) / n(Li2O)≤2.30, more preferably, 2.02≤n(SiO2) / n(Li2O)≤2.20; and / or,
[0084] 90%≤n(SiO2)+n(Li2O)≤95%, preferably, 90%≤n(SiO2)+n(Li2O)≤92%; wherein n(SiO2) is the molar percentage content of SiO2 at the center of the chemically strengthened glass-ceramics, and n(Li2O) is the molar percentage content of Li2O at the center of the chemically strengthened glass-ceramics. In the present application, by adjusting and controlling the content relationship of SiO2 and Li2O, it is beneficial to ensure that a glass-ceramics that meets the desired performance and has lithium disilicate as the main crystalline phase structure is obtained, and at the same time, it is beneficial to achieve a desired stress distribution structure.
[0085] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies:
[0086] The value of n(SiO2) / n(Li2O) is 2.08, 2.09 or 2.12; and / or,
[0087] The value of n(SiO2)+n(Li2O) is 90.19%, 90.4%, 90.62%, 90.82%, 91.24% or 91.62%; wherein n(SiO2) is the molar percentage content of SiO2 at the center of the chemically strengthened glass-ceramics, and n(Li2O) is the molar percentage content of Li2O at the center of the chemically strengthened glass-ceramics.
[0088] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in terms of mass percentage of oxides, comprises:
[0089] SiO2: 60% to 70%, Al2O3: 0% to 6%, P2O5: 2% to 8%, ZrO2: 8% to 12%, Li2O: 10% to 20%, SrO: 0% to 6%, Na2O: 0% to 3%. In the present application, by adjusting and controlling the content range of each oxide component, it is beneficial to ensure that the chemically strengthened microcrystalline glass that meets the desired crystal phase structure and stress structure is obtained.
[0090] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in terms of mass percentage of oxides, further comprises:
[0091] K2O: 0% to 2%, CaO: 0% to 2%, B2O3: 0% to 1%, Ta2O5: 0% to 2%, BaO: 0% to 6%.
[0092] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in terms of mass percentage of oxides, comprises:
[0093] The mass percentage of SiO2 is 62% to 68%, preferably 63% to 67%; and / or,
[0094] The mass percentage of Al2O3 is 1% to 6%, preferably 2% to 6%, more preferably 2% to 3%; and / or,
[0095] The mass percentage of P2O5 is 3% to 6%, preferably 3% to 5%, more preferably 4% to 5%; and / or,
[0096] The mass percentage of ZrO2 is 8% to 11%, preferably 9% to 11%; and / or,
[0097] The mass percentage of Li2O is 11% to 18%, preferably 12% to 16%, more preferably 14% to 16%; and / or,
[0098] The mass percentage of SrO is 0% to 5%, preferably 0% to 4%; and / or,
[0099] The mass percentage of Na2O is 0% to 2.8%, preferably 0% to 1%; and / or,
[0100] The mass percentage of K2O is 0% to 1.5%, preferably 0% to 1.2%; and / or,
[0101] The mass percentage of CaO is 0% to 1%, preferably 0% to 0.95%; and / or,
[0102] The mass percentage of B2O3 is 0% to 0.8%, preferably 0% to 0.6%; and / or,
[0103] The mass percentage of Ta2O5 is 0% to 1.8%, preferably 0% to 1.5%; and / or,
[0104] The mass percentage of BaO is 0% to 5.5%, preferably 0% to 5%.
[0105] In some embodiments of the present application, the crystallinity of the chemically strengthened glass-ceramics is not less than 60%, preferably, the crystallinity of the chemically strengthened glass-ceramics is 70% to 90%, and more preferably, the crystallinity of the chemically strengthened glass-ceramics is 70% to 80%; and / or,
[0106] In the chemically strengthened glass-ceramics, the average grain size does not exceed 50 nm, preferably, the average grain size is 10 nm to 40 nm, and more preferably, the average grain size is 15 nm to 30 nm; and / or,
[0107] In the chemically strengthened glass-ceramics, the mass of lithium disilicate crystal phase accounts for 80wt% to 100wt% of all crystal phases; and / or,
[0108] The mass percentage of the petalite crystalline phase in the chemically strengthened microcrystalline glass is less than or equal to 10%, preferably less than or equal to 5%, and more preferably, does not contain the petalite crystalline phase. The present application helps the microcrystalline glass to maintain excellent optical properties while satisfying excellent mechanical strength properties and high intrinsic strength by making the microcrystalline glass meet the desired crystallinity and / or desired crystal phase composition and / or appropriate average grain size.
[0109] In some embodiments of the present application, when the thickness does not exceed 0.70 mm, the b value of the chemically strengthened glass-ceramics is less than 1.0, preferably, the b value is less than 0.8, and more preferably, the b value is ≤ 0.6; and / or,
[0110] The chemically strengthened microcrystalline glass is transparent in the visible light wavelength range. Preferably, for light with a wavelength of 550 nm, the transmittance of the chemically strengthened microcrystalline glass is ≥85%, preferably, the transmittance is ≥90%, and more preferably, the transmittance is ≥90.2%. Chemically strengthened microcrystalline glass that meets the b value and / or transmittance can ensure good display effect and transparency effect, and is suitable for use in electronic device display screens that require display effect.
[0111] In some embodiments of the present application, the Young's modulus of the chemically strengthened glass-ceramics is not less than 100 GPa, preferably, the Young's modulus is not less than 110 GPa, and more preferably, the Young's modulus is 110 GPa to 130 GPa; and / or,
[0112] The density of the chemically strengthened glass-ceramics is not less than 2.54 g / cm 3 , preferably, the density is 2.54 g / cm 3 ~2.64g / cm 3 and / or,
[0113] The refractive index of the chemically strengthened glass-ceramics is ≤1.60, preferably, the refractive index is 1.55 to 1.60; and / or,
[0114] The Vickers hardness of the chemically strengthened glass-ceramics is ≥700kgf / mm 2 , preferably, the Vickers hardness is 700kgf / mm 2 ~850kgf / mm 2 The Young's modulus, density, Vickers hardness, and refractive index are within the above ranges, indicating that the chemically strengthened glass-ceramics has a high intrinsic strength, which is conducive to achieving excellent mechanical strength properties and excellent damage resistance.
[0115] In some embodiments of the present application, the thickness t of the chemically strengthened glass-ceramics is 0.35 mm to 1.0 mm, preferably, the thickness t is 0.4 mm to 0.7 mm, and more preferably, the thickness t is 0.45 mm to 0.55 mm; and / or, the chemically strengthened glass-ceramics is 2D, 2.5D, 3D or special-shaped; and / or, the chemically strengthened glass-ceramics is of equal thickness or unequal thickness. Those skilled in the art can choose according to their needs. "Unequal thickness" means that the glass-ceramics or chemically strengthened glass-ceramics contain at least two parts with different thicknesses.
[0116] In some embodiments of the present application, the chemically strengthened glass-ceramics is subjected to a sandpaper drop resistance test, and the sandpaper used is 80-mesh sandpaper. When the thickness does not exceed 0.70 mm, preferably when the thickness is 0.4 mm to 0.7 mm, and more preferably when the thickness is 0.45 mm to 0.55 mm, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥ 1.60 m, and preferably, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is 1.65 m to 2.50 m. The larger the measured average sandpaper drop resistance height value, the better the drop damage resistance of the chemically strengthened glass-ceramics.
[0117] In some embodiments of the present application, a 10 mm diameter round-head metal pressure rod is used to squeeze the chemically strengthened glass-ceramics, and the single-rod static pressure strength that the chemically strengthened glass-ceramics can withstand is tested. The average value of the single-rod static pressure strength that the chemically strengthened glass-ceramics can withstand is greater than 200 N, preferably greater than 230 N. The larger the measured single-rod static pressure strength that can be sustained, the better the anti-extrusion damage performance of the chemically strengthened glass-ceramics.
[0118] In a second aspect, a glass device is provided, wherein the glass device comprises the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0119] In a third aspect, a cover glass is provided, the cover glass comprising the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect. The cover glass may be a display cover, a back cover or a camera protection cover of an electronic device.
[0120] In a fourth aspect, an electronic device is provided, the electronic device comprising the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0121] In some embodiments of the present application, the electronic device includes a housing assembled on the outside of the electronic device, and the housing includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0122] In some embodiments of the present application, the housing includes a display cover assembled on the front side of the electronic device, and the display cover includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0123] In some embodiments of the present application, the housing includes a back cover assembled on the back side of the electronic device, and the back cover includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0124] In some embodiments of the present application, the electronic device also includes a camera assembly located inside the housing, the housing includes a camera protection cover, the camera protection cover is covered on the camera assembly, and the camera protection cover includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0125] In some embodiments of the present application, the electronic device further includes a middle frame located between the display module and the housing, and the middle frame includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0126] In some embodiments, the housing may be partially or entirely made of chemically strengthened glass-ceramics. The electronic device in the present application may be a display cover, a back cover, a camera protection cover, or a middle frame, wherein one or more of the above may be made of chemically strengthened glass-ceramics as described in any embodiment of the first aspect.
[0127] One or more of the above technical solutions provided by the present application have the following advantages compared with the prior art:
[0128] The present application makes the chemically strengthened glass-ceramics satisfy a specific crystal phase structure and stress distribution structure, so that the chemically strengthened glass-ceramics have both excellent damage resistance and high safety performance. The chemically strengthened glass-ceramics can achieve excellent anti-fall damage performance, and when it encounters impact and shattering, the generated fragments are relatively large, and a large number of small fragments that are easy to splash around will not be formed, which can avoid safety hazards and meet emergency use needs after breaking. For example, in the present application, by making the tensile stress line density value of the chemically strengthened glass-ceramics whose main crystal phase is the lithium disilicate crystal phase and the ratio of the stress integral to the thickness t of the tensile stress layer near the middle position satisfy a specific difference relationship, the chemically strengthened glass-ceramics satisfies a specific stress distribution structure, and while ensuring that the chemically strengthened glass-ceramics has a higher overall stress level, it can ensure that the internal stress distribution of the chemically strengthened glass-ceramics is safer, thereby facilitating the chemically strengthened glass-ceramics to maintain a safe stress state. BRIEF DESCRIPTION OF THE DRAWINGS
[0129] The accompanying drawings herein are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the specification are used to explain the principles of the present application. It should be understood that the following drawings only illustrate certain embodiments of the present application and therefore should not be considered to limit the scope of the present application.
[0130] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0131] Figure 1 is a DSC curve diagram of the substrate glass of Example 13 of the present application;
[0132] Figure 2This is the XRD graph of the glass-ceramics of Example 13 of the present application;
[0133] Figure 3 This is a comparison diagram of XRD curves of the glass-ceramics of Example 13 of the present application and the chemically strengthened glass-ceramics;
[0134] Figure 4 is a transmittance curve diagram of the glass-ceramics of Example 13 of the present application;
[0135] Figure 5 This is a comparison chart of transmittance curves of the glass-ceramics of Example 13 of the present application and the chemically strengthened glass-ceramics;
[0136] Figure 6 is a curve showing a change in stress versus thickness of the chemically strengthened glass-ceramics of Example 13 of the present application;
[0137] Figure 7 The stress-thickness variation curves of the chemically strengthened glass-ceramics of Example 3, Example 4, Comparative Example 4 and Comparative Example 5 of the present application are shown;
[0138] Figure 8 This is a vertical projection diagram of the fragment particles on a two-dimensional plane after the chemically strengthened glass-ceramics of Example 13 of the present application is broken in a drop test;
[0139] Fig. 9 This is a vertical projection diagram of the fragment particles on a two-dimensional plane after the chemically strengthened glass-ceramics of Example 14 of the present application is broken in a drop test;
[0140] Fig.10 This is a vertical projection diagram of the fragment particles on a two-dimensional plane after the chemically strengthened microcrystalline glass of Comparative Example 6 of the present application is broken in a drop test;
[0141] Fig.11 This is a vertical projection diagram of the fragment particles on a two-dimensional plane after the chemically strengthened microcrystalline glass of Comparative Example 12 of the present application is broken in a drop test;
[0142] Fig.12 This is a schematic diagram of the front structure of the electronic device mentioned in the embodiment of the present application;
[0143] Fig.13 A schematic diagram of the rear structure of the electronic device mentioned in the embodiment of the present application;
[0144] Fig.14 The structure of the electronic device mentioned in the embodiment of this application is schematically shown. Figure 1 ;
[0145] Fig.15 The structure of the electronic device mentioned in the embodiment of this application is schematically shown. Figure 2 ;
[0146] Fig.16 Schematic diagram of the structure of the chemically strengthened microcrystalline glass of the present application, wherein t is the thickness of the glass, d is the depth of the compressive stress layer, 21 is the compressive stress layer, and 22 is the tensile stress layer.
[0147] Figure numerals: 1-housing; 11-display screen cover; 12-back cover; 13-camera protection cover; 2-camera assembly; 3-middle frame; 4-display module. DETAILED DESCRIPTION
[0148] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0149] The endpoints and any values of the ranges disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all refer to including or not including (or may have or may not have). "And / or" as referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0150] Explanation of terms and test methods:
[0151] In the present application, glass-ceramics is a type of solid composite material that is prepared by targeted controlled heat treatment of substrate glass and contains both a glass phase and a crystal phase (also called a microcrystalline phase or a crystal phase). Glass-ceramics are also called glass ceramics or crystallized glass.
[0152] In the present application, chemically strengthened glass-ceramics refers to a solid composite material obtained after chemical strengthening treatment of glass-ceramics. It should be understood that during chemical strengthening treatment, alkali metal ions with large ionic radius (such as potassium ions or sodium ions) in the molten salt bath (or also called molten salt bath) will replace alkali metal ions with small ionic radius (such as sodium ions or lithium ions) in the glass-ceramics, thereby generating an exchange ion volume difference and generating compressive stress (or also called compressive stress) on the surface of the glass-ceramics.
[0153] In the present application, substrate glass (or also referred to as base glass) refers to glass that has not been subjected to nucleation treatment, crystallization treatment, and strengthening treatment.
[0154] In the present application, nucleation treatment refers to growing crystal nuclei in the substrate glass by heat treatment; crystallization treatment refers to precipitating target crystals or crystalline phases in the substrate glass by heat treatment.
[0155] In the present application, the composition at the center of the chemically strengthened glass-ceramics refers to the composition at the center of the depth or thickness of the chemically strengthened glass-ceramics or near the center of the depth or thickness, that is, the composition of the region in the chemically strengthened glass-ceramics where ion exchange has not been performed. It should be understood that the composition at the center of the chemically strengthened glass-ceramics is the same or substantially the same as the composition of the glass-ceramics used to prepare the chemically strengthened glass-ceramics but which has not yet been chemically strengthened.
[0156] In the present application, the visible light wavelength range refers to 360nm to 740nm.
[0157] In the present application, the main crystalline phase (or also referred to as the main crystalline phase) refers to a crystalline phase having a higher mass content (or also referred to as weight percentage, mass percentage) than other crystalline phases present in the microcrystalline glass or chemically strengthened microcrystalline glass.
[0158] In the present application, the main surface refers to the surface with the largest surface area, such as the upper surface or lower surface of a horizontally placed microcrystalline glass sheet.
[0159] In the present application, crystallinity refers to the percentage of the total mass of the crystalline phase in the microcrystalline glass or chemically strengthened microcrystalline glass to the mass of the microcrystalline glass or chemically strengthened microcrystalline glass, or is also called the total content of the crystalline phase in the microcrystalline glass or chemically strengthened microcrystalline glass.
[0160] In the present application, when light of a certain wavelength is irradiated onto the main surface of microcrystalline glass or chemically strengthened microcrystalline glass, the light will be reflected, absorbed and transmitted, and the ratio of the intensity of the transmitted part to the intensity of the incident light is the transmittance.
[0161] In this application, the refractive index refers to the ratio of the propagation speed of light in a vacuum to the propagation speed of light in the medium.
[0162] In the present application, the crystallized glass raw material refers to the glass raw material which has reached a certain degree of crystallinity after a period of heat treatment, but has not yet reached the target crystallinity, and can continue to crystallize to reach the target crystallinity when heated.
[0163] In this application, CT_LD refers to the tensile stress linear density, with the unit of MPa / mm. In this application, CT_LD is calculated by the following formula:
[0164]
[0165] Wherein, t is the thickness of chemically strengthened glass-ceramics, in mm; DOL_0 is the depth of the compressive stress layer of chemically strengthened glass-ceramics, in μm; |CT_AV| is the absolute value of the average tensile stress of chemically strengthened glass-ceramics, in MPa. It should be understood that in the calculation formula of tensile stress line density, the data is substituted into the calculation according to the above unit requirements, and the calculation result is obtained, and the unit does not participate in the calculation. In this application, the tensile stress line density value is basically the ratio of the definite integral of the tensile stress curve to the thickness of the chemically strengthened glass-ceramics.
[0166] It should be understood that after the glass-ceramics is placed in a molten salt bath for ion exchange, a compressive stress layer (or also called a compressive stress layer) will be formed on the surface of the glass-ceramics, and a tensile stress layer (or also called a tensile stress layer) will be formed inside the glass-ceramics. Exemplarily, during the chemical strengthening treatment, the alkali metal ions with a large radius in the molten salt bath are ion-exchanged with the alkali metal ions with a small radius in the glass-ceramics, thereby forming a compressive stress layer on the surface of the glass-ceramics and a tensile stress layer inside the glass-ceramics, that is, after the chemical strengthening treatment of the glass-ceramics, a chemically strengthened glass-ceramics containing a compressive stress layer and a tensile stress layer is prepared.
[0167] In the present application, CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened microcrystalline glass, in MPa, obtained by testing with an SLP-2000 stress meter (or also known as a scattered light photoelastic stress meter).
[0168] In this application, |CT_CV| refers to the absolute value of the maximum tensile stress, in MPa, obtained by testing with an SLP-2000 stress meter.
[0169] In this application, |CT_AV| refers to the absolute value of the average tensile stress, in MPa, specifically the absolute value of the average value of all tensile stresses in the tensile stress layer, obtained by testing with an SLP-2000 stress meter.
[0170] In this application, DOL_0 refers to the depth of the compressive stress layer, or the depth of the compressive stress layer, specifically the distance from any main surface of the chemically strengthened microcrystalline glass to the position where the compressive stress close to the surface is zero, obtained by testing with an SLP-2000 stress meter.
[0171] In this application, the test method of the aforementioned stress performance is as follows: SLP-2000 stress meter is used for testing, the wavelength of the light source is 518nm, SOC=25.5 (nm / cm) / MPa, the refractive index is set according to the refractive index value of the sample to be tested, and the exposure time is 300usec. When testing the stress performance of chemically strengthened microcrystalline glass, it is necessary to first drop a conductive liquid on the stress meter, then wipe the chemically strengthened microcrystalline glass sample to be tested clean, place it on the test path, and test its stress value. Among them, the stress meter is SLP-2000 and the conductive liquid used is a conductive liquid with a refractive index of 1.51. Then, the tensile stress line density (CT_LD) value of the chemically strengthened microcrystalline glass is calculated by the calculation formula of the aforementioned tensile stress line density; the stress data of the chemically strengthened microcrystalline glass measured by SLP-2000 is used to calculate the stress integral value of the tensile stress layer from 2 times DOL_0 of the main surface of the chemically strengthened microcrystalline glass to half the thickness of the chemically strengthened microcrystalline glass.
[0172] In this application, the b value is used to characterize the yellow-blue value of a material. The b value in this application is the b value of transmitted light, and a positive b value indicates that the material is blue.
[0173] In this application, M K2O is the mass percentage of K2O on the surface of chemically strengthened glass-ceramics, M' K2O is the mass percentage of K2O on the surface of the chemically strengthened micro-ceramic glass after thinning by 3 μm on both main surfaces of the chemically strengthened micro-ceramic glass along the thickness direction, M Na2O is the mass percentage of Na2O on the surface of chemically strengthened glass-ceramics, M' Na2O It is the mass percentage of Na2O on the surface of the chemically strengthened microcrystalline glass after thinning the two main surfaces of the chemically strengthened microcrystalline glass by 3μm along the thickness direction.
[0174] M K2O The test method is as follows: The K element content on the surface of the chemically strengthened microcrystalline glass is measured by an X-ray fluorescence spectrometer (XRF), and then the mass percentage of K2O on the surface is calculated. The calculation method is: the mass percentage of K2O on the surface = (the K element content on the surface × the relative molecular mass of K2O) / (the relative atomic mass of the K element × 2). It should be understood that the K element content on the surface = the mass of the K element / the total mass of the element, and the total mass of the element = the total mass of the oxide. The model of the X-ray fluorescence spectrometer (XRF) used is Thermo Scientific ARL PERFORM'X, the target material is Rh (rhodium), the light tube voltage is 40kV, the current is 60mA, the collimator is 0.15, the crystal is LiF200, the detector is FPC, the test range is a circle with a diameter of 29mm, and the test method adopts the X_UQ method in the OXSAS analysis software.
[0175] M Na2O Test method: The surface Na content in the chemically strengthened microcrystalline glass is measured by X-ray fluorescence spectrometer (XRF), and then the mass percentage of Na2O on the surface is calculated. The calculation method is: surface Na2O mass percentage = (surface Na content × relative molecular mass of Na2O) / (relative atomic mass of Na element × 2). It should be understood that the surface Na content = Na element mass / total element mass, and the total element mass = total oxide mass. The X-ray fluorescence spectrometer (XRF) used is Thermo Scientific ARL PERFORM'X, the target material is Rh (rhodium), the light tube voltage is 30kV, the current is 80mA, the collimator is 0.40, the crystal is AxO3, the detector is FPC, the test range is a circle with a diameter of 29mm, and the test method uses the X_UQ method in the OXSAS analysis software.
[0176] In this application, the XRF instrument is tested using a non-standard test, and the concentration of elements or their oxides with atomic numbers 6 and below in the chemically strengthened microcrystalline glass is not tested. The mass percentage of K2O on the surface of the chemically strengthened microcrystalline glass = the mass of K2O / the total mass of the oxides, and the mass percentage of Na2O on the surface of the chemically strengthened microcrystalline glass = the mass of Na2O / the total mass of the oxides, where the oxides include SiO2, Al2O3, ZrO2, Na2O, K2O, P2O5 and other oxides that can be accurately tested by XRF, and do not include B2O3, Li2O and other oxides that cannot be accurately tested by XRF. M' K2O and M' Na2O For the test method, see M K2O and M Na2O Testing method.
[0177] In this application, the thickness is obtained by micrometer testing. It should be understood that in the thickness direction of the glass-ceramic sample, the degree of ion exchange changes gradually from the surface to the center, and the overall Na-K and / or Li-Na exchange amount increment (mass) generally does not exceed 1.5% of the total mass of the sample. Therefore, the expansion effect in the thickness direction is extremely slight, and it can be approximately considered that the thickness has basically not changed. That is, before and after chemical strengthening, the thickness of the glass-ceramic changes very little, which can be basically ignored, and the thickness of the glass-ceramic is basically the same as the thickness of the chemically strengthened glass-ceramic obtained therefrom.
[0178] In this application, the size specifications of the microcrystalline glass sheet are tested using a two-dimensional measuring machine (instrument model: MiyuMY-YXCL-4030).
[0179] In this application, Young's modulus is used to characterize the ability of glass to resist elastic deformation due to external force. This application uses UMS-100 ultrasonic material characterization system to test the Young's modulus of microcrystalline glass by sound waves.
[0180] In this application, the crystal phase, crystallinity and average grain size of the microcrystalline glass or chemically strengthened microcrystalline glass are confirmed by XRD testing. Specifically:
[0181] (1) XRD test: The glass-ceramics or chemically strengthened glass-ceramics of the present application is crushed and ground into a sample with a particle size of less than 75 μm, and the ground sample is tested using an X-ray diffractometer to obtain an XRD diffraction peak curve and XRD diffraction data. The X-ray diffractometer used in the present application is Shimadzu XRD-6100, the target material is copper, 2θ=10°-50°, the scanning speed is 0.2° / min, the operating voltage is 40 kV, and the operating current is 30 mA.
[0182] (2) Determination of crystalline phase: XRD diffraction data were analyzed using Jade software (JADE Standard 8.6) to determine the crystalline phase in the sample.
[0183] (3) Determination of crystallinity (also known as total crystalline content): The XRD test results (RAW format) are imported into the Jade software for fitting and calculation to determine the crystallinity of the sample. Specifically, the ratio of the fitted crystalline phase peak area to the fitted total peak area is recorded as the crystallinity of the sample.
[0184] (4) Determination of average grain size (or also called average crystal size): The average grain size of the sample can be calculated using the result data obtained from the XRD test according to the Scherrer formula D = Kλ / (βcosθ). Wherein, λ is the wavelength of the X-ray, λ = 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW format file output by the XRD instrument is curve fitted in the Jade software, and Jade outputs a fitting report. According to the angle 2θ value and PeakFWHM value corresponding to each diffraction peak in the fitting report, the PeakFWHM value is converted into radians: β = (FWHM / 180×3.14), and the grain size of each diffraction peak is calculated by the Scherrer formula D = Kλ / (βcosθ) and then averaged to obtain the average grain size in the sample.
[0185] In this application, with reference to the national standard "GB / T7962.12-2010 Test Method for Colorless Optical Glass Part 12: Spectral Transmittance", a haze meter is used to test the transmittance and b value of the microcrystalline glass of this application. Specifically, the haze meter is used to test the transmittance and b value of 5 microcrystalline glass pieces of the same batch to light of different wavelengths. The average value of the b values measured for the 5 microcrystalline glass pieces is taken as the b value result of the microcrystalline glass. The average value of the transmittance of the 5 microcrystalline glass pieces under 550nm wavelength light is taken as the transmittance result of the microcrystalline glass under 550nm wavelength light. The haze meter used in the test of this application is a Konica Minolta spectrophotometer CM-3600A in Japan, the optical system for receiving light is transmission, the splitting mode is a plane refractive grating, the wavelength range is 360nm-740nm, the wavelength spacing is 10nm, the illumination light source is a pulse xenon lamp × 4, the ambient temperature of the instrument is 24℃, and the air humidity is 40%.
[0186] In the present application, Shimadzu's UV-2600 ultraviolet-visible spectrophotometer is also used to test the transmittance curve of the microcrystalline glass or chemically strengthened microcrystalline glass under the wavelength light in the visible light wavelength range.
[0187] Density test: In this application, the electronic density balance SD-200L of Japan ALFAMIRAGE is used to test the density of microcrystalline glass.
[0188] Refractive index test: In this application, the refractive index of microcrystalline glass was tested using Abbe refractometer WYA-2WAJ produced by Shanghai Lichen Bangxi Instrument Technology Co., Ltd., China.
[0189] Thermal expansion softening point test: The sample is made into a cylinder with a diameter of 5.5mm and a length of 20mm, and the sample is tested using a thermal expansion instrument LINSEISL75VD1000 to output a thermal expansion test curve. The temperature corresponding to the peak position of the curve is the thermal expansion softening point temperature of the sample.
[0190] Vickers hardness test: The chemically strengthened microcrystalline glass is made into a small piece with a length, width and thickness of 50mm×50mm×(0.47~0.54)mm, and a glass sample with a clean surface and no visible scratches, pits, cracks and other damage is selected as a test sample, and then the Vickers hardness is measured using a Vickers hardness tester. The Vickers hardness tester used in the test of this application is a digital display small load Vickers hardness tester model VTD405 of Beijing Kewei Technology Co., Ltd. Test conditions: load 300gf, load time 10s, the effectiveness of the indentation complies with the "GB / T37900-2019 Ultra-thin glass hardness and fracture toughness test method small load Vickers hardness indentation method" standard. Select 3 different positions on the surface of the same test sample for measurement, and take the average of the 3 measurement results as the Vickers hardness result of the test sample.
[0191] Single rod static pressure test: Place the glass sample to be tested on the bottom ring of the tensile testing machine (LT-850A), start the test software, and set the moving speed of the extrusion rod (rod diameter 10mm, ball head diameter 10mm) to 10mm / min. Click to start the test. The extrusion rod will apply force to the center of the glass sample to be tested at the set moving speed until the glass sample cracks and breaks. The test software will automatically read the force (N) when the glass sample breaks, and record it as the single rod static pressure strength it can withstand as the test result. Take 10 glass samples in the same state for testing, and take the average value of the test results as the single rod static pressure strength of the glass sample to be tested.
[0192] Average sandpaper drop height test: In this application, the sum of the sandpaper drop heights measured for each of the multiple chemically strengthened glass-ceramics samples in the same embodiment or the same comparative example is divided by the number of samples measured, and the value obtained is recorded as the average sandpaper drop height of the tested chemically strengthened glass-ceramics, which is used to characterize the drop damage resistance of the chemically strengthened glass-ceramics. The drop damage resistance here is obtained by using uniform sandpaper testing, which can simulate the application scenario of chemically strengthened glass-ceramics falling onto a ground with relatively uniform roughness.
[0193] Specifically, at least 10 samples were taken from each batch for testing, and the average sandpaper drop height was
[0194] Where n is the number of glass samples tested in each batch, and hi is the sandpaper drop resistance height of a single sample test.
[0195] Among them, the test method for the sandpaper drop height of a single sample is:
[0196] Step 1: Stick 80-grit sandpaper on the lower surface of the 181g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine;
[0197] Step 2: Place the chemically strengthened glass-ceramic sample to be tested directly under the model machine, with the chemically strengthened glass-ceramic sample facing the sandpaper, specifically, with the main surface of the chemically strengthened glass-ceramic facing the sandpaper. Make the model machine fall from a certain drop height to impact the chemically strengthened glass-ceramic sample directly under the model machine. If the chemically strengthened glass-ceramic sample does not break, increase the drop height of the model machine in a certain pattern, and make the model machine continue to fall, impacting the chemically strengthened glass-ceramic sample directly under the model machine, until the chemically strengthened glass-ceramic sample breaks. For example, the drop height of the model machine starts from 0.4m, and the sample is dropped once. If the sample does not break, the drop height of the model machine is increased by 0.1m, and it falls again. Repeat the above process until the chemically strengthened glass-ceramic sample breaks;
[0198] Step 3: The last drop height of the chemically strengthened microcrystalline glass sample before it breaks is recorded as its anti-sandpaper drop height. For example, if the drop height is increased by 0.1m each time, when the drop height of the sample is 0.5m when it breaks, the anti-sandpaper drop height of the sample is 0.4m.
[0199] The average size of the longest side of the fragments is tested by first testing the average sandpaper drop height on 80-grit sandpaper. When the glass falls and breaks, take photos of the broken results and import them into the particle size analysis and calculation software (such as Nanomeasure) for analysis. During the analysis, more than 80% of the glass fragments are selected for marking, and the longest side of the selected glass fragments under the two-dimensional vertical projection is required to be relatively large. The analysis and calculation software will automatically calculate and output the average value of the maximum size of the selected glass fragments.
[0200] Without being limited by any theory, for lithium disilicate glass-ceramics with a high lithium content, the improvement of the overall stress level does not necessarily ensure that it obtains excellent damage resistance. If during strengthening, only the improvement of the overall stress level is paid attention to, but not the stress distribution, it is often easy to have inappropriate stress distribution in the obtained chemically strengthened glass-ceramics, resulting in the phenomenon of "reduced strengthening stability". When the overall stress level is increased, the internal tensile stress is too large, especially the tensile stress in a certain area inside is too large. Such a stress distribution structure not only cannot ensure that the chemically strengthened glass-ceramics achieves excellent damage resistance, but also brings safety hazards, causing the chemically strengthened glass-ceramics to be prone to explosive cracking under slight impact, small fragments to fly everywhere, and even prone to self-explosion, which will seriously affect the reliability of chemically strengthened glass-ceramics products and have a serious impact on the personal safety of users.
[0201] In view of this, for microcrystalline glass with lithium disilicate as the main crystalline phase, the present application makes the chemically strengthened microcrystalline glass meet specific stress characteristics and has a specific stress distribution structure. While ensuring the improvement of the mechanical strength performance of the chemically strengthened microcrystalline glass and improving its damage resistance, the chemically strengthened microcrystalline glass maintains a safe stress state and has higher safety performance.
[0202] The chemically strengthened microcrystalline glass with specific stress characteristics provided by the present application has excellent resistance to drop damage, and when the chemically strengthened microcrystalline glass is dropped and broken, the fragments produced are relatively large, and a large number of small fragments that are easy to fly around will not be formed, which can avoid safety hazards. When the chemically strengthened microcrystalline glass is used as the cover glass of the display screen, it can also meet the emergency use needs after falling and breaking.
[0203] As described above, in some embodiments of the present application, a chemically strengthened glass-ceramic is provided, wherein the chemically strengthened glass-ceramic contains a lithium disilicate crystalline phase, wherein the lithium disilicate crystalline phase has a higher mass percentage than other crystalline phases present in the chemically strengthened glass-ceramic;
[0204] The chemically strengthened glass-ceramics has a compressive stress layer on the surface and a tensile stress layer inside;
[0205] The chemically strengthened glass-ceramics satisfies the following relationship:
[0206] A ≥ 49500, preferably A ≥ 50000, more preferably A ≥ 51000, more preferably the value of A is 49500 to 65000;
[0207] Wherein, CT_LD is the tensile stress linear density, in MPa / mm, CT_LD≥60000MPa / mm,
[0208] t is the thickness of chemically strengthened glass-ceramics, in mm,
[0209] is the ratio of the stress integral of the tensile stress layer from 2 times DOL_0 from the main surface of the chemically strengthened glass-ceramics to the position half the thickness of the chemically strengthened glass-ceramics along the thickness direction of the chemically strengthened glass-ceramics to the thickness t, in units of MPa / mm, where x is the depth from the main surface of the chemically strengthened glass-ceramics,
[0210] In relational formula A, the data is substituted into the calculation according to the above-mentioned unit requirements, and the calculation results are obtained. The units do not participate in the calculation. The A value represents the tensile stress line density (in the present application, the tensile stress line density value is basically approximately the ratio of the definite integral of the tensile stress curve to the thickness of the chemically strengthened microcrystalline glass) minus the ratio of the stress integral of the tensile stress layer from 2 times DOL_0 from the main surface of the chemically strengthened microcrystalline glass to half the thickness of the chemically strengthened microcrystalline glass to the thickness t.
[0211] The present application satisfies a specific stress distribution structure by making the tensile stress line density value of the chemically strengthened microcrystalline glass whose main crystal phase is the lithium disilicate crystal phase and the ratio of the stress integral of the tensile stress layer near the middle position to the thickness t satisfy a specific difference relationship. While ensuring that the chemically strengthened microcrystalline glass has a higher overall stress level, the internal stress distribution of the chemically strengthened microcrystalline glass can be guaranteed to be safer, thereby facilitating the chemically strengthened microcrystalline glass to maintain a safe stress state. The chemically strengthened microcrystalline glass of the present application can not only achieve excellent damage resistance, such as excellent resistance to drop damage, but also has high safety performance. When it encounters impact and breakage, the fragments generated are relatively large, and a large number of small fragments that are easy to splash around will not be formed, which can avoid safety hazards and meet emergency use needs after breaking.
[0212] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 60000.00MPa / mm≤CT_LD, preferably, 65000.00MPa / mm≤CT_LD≤90000.00MPa / mm, and more preferably, 70000.00MPa / mm≤CT_LD≤90000.00MPa / mm, wherein CT_LD refers to the tensile stress linear density. Controlling the CT_LD of the chemically strengthened glass-ceramics to a relatively large value, for example, not less than 60000MPa / mm, is conducive to ensuring that the tensile stress stored inside the chemically strengthened glass-ceramics is sufficiently dense, and thus is conducive to ensuring that it has a higher surface stress level, ensuring that it can obtain excellent damage resistance, such as excellent drop damage resistance, to meet market demand.
[0213] In some embodiments, the CT_LD of the chemically strengthened glass-ceramics may be 60000 MPa / mm to 72000 MPa / mm, 62000 MPa / mm to 70000 MPa / mm, 64000 MPa / mm to 85000 MPa / mm, or 75000 MPa / mm to 80000 MPa / mm. In some embodiments, the CT_LD of the chemically strengthened glass-ceramics may be 60000 MPa / mm, 65000 MPa / mm, 66000 MPa / mm, 67000 MPa / mm, 68000 MPa / mm, 69000 MPa / mm, 70000 MPa / mm, 72000 MPa / mm, 74000 MPa / mm, 76000 MPa / mm, 78000 MPa / mm, 80000 MPa / mm, 85000 MPa / mm, 90000 MPa / mm, 81333.56 MPa / mm, 77092.45 MPa / mm, 82483. 27MPa / mm, 80204.48MPa / mm, 78205.39MPa / mm, 84212.52MPa / mm, 81170.89MPa / mm, 81403.23MPa / mm, 79173.31MPa / mm, 78723.70MPa / mm, 79309.57MPa / mm, 77483.48MPa / mm, 77692.71MPa / mm or 72249.87MPa / mm, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0214] In some embodiments, the value of relation A may be: 49500, 50000, 50500, 51000, 51500, 52000, 52500, 53000, 53500, 54000, 54500, 55000, 55500, 56000, 56500, 57000, 57500, 58000, 58500, 59000, 59500, 60000, 65000, 54800, 51000, 89000, 89000, 90000, 91000, 92000, 93000, 94000, 95000. 4.81, 57170.35, 52689.22, 52272.54, 58526.63, 54807.04, 56429.32, 52815.28, 53580.63, 54032.42, 54060.10, 53361.40 or 54841.31, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained.
[0215] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies the following relationship:
[0216] B=[|CT_AV|×(t / 2-DOL_0)]×[5×M K2O / (5×M K2O +0.5×M Na2O )], B ≥ 9000 MPa·μm, preferably,
[0217] B ≥ 9100 MPa·μm, more preferably, B ≥ 9200 MPa·μm, more preferably, the value of B is 9000 MPa·μm to 13000 MPa·μm;
[0218] Where |CT_AV| is the absolute value of the average tensile stress,
[0219] t is the thickness of chemically strengthened glass-ceramics,
[0220] M K2O is the mass percentage of K2O on the surface of chemically strengthened glass-ceramics,
[0221] M Na2O is the mass percentage of Na2O on the surface of chemically strengthened glass-ceramics.
[0222] The present application enables the chemically strengthened microcrystalline glass to have an optimal stress level by ensuring that the chemically strengthened microcrystalline glass has good single-rod static pressure resistance and high hardness by satisfying a specific relationship between the stress characteristics and the surface component content of the chemically strengthened microcrystalline glass.
[0223] In some embodiments, the value of relational expression B may be: 9000.00 MPa·μm, 9500.00 MPa·μm, 10000.00 MPa·μm, 10500.00 MPa·μm, 11000.00 MPa·μm, 11500.00 MPa·μm, 12000.00 MPa·μm, 13000.00 MPa·μm, 10333.74 MPa·μm, 11642.77 MPa·μm, 11864.03 MPa·μm, 10818.69 MPa·μm, 1019 9.45MPa·μm, 10638.55MPa·μm, 10862.45MPa·μm, 9442.20MPa·μm, 9292.34MPa·μm, 10157.90MPa·μm, 10637.99MPa·μm, 10907.18MPa·μm, 10429.05MPa·μm or 11586.62MPa·μm, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0228] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies the following relationship: C=CS_50 / |CT_CV|, C≥0.85, preferably 0.85-1.5, more preferably 0.9-1.3, more preferably 0.9-1.2; wherein CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened glass-ceramics, in MPa, and |CT_CV| is the absolute value of the maximum tensile stress, in MPa. The present application facilitates the chemically strengthened glass-ceramics to have a better stress level by satisfying a specific relationship between the stress characteristics of the chemically strengthened glass-ceramics, thereby facilitating the realization that even after being broken, its fragments are relatively large, and a large number of small fragments that are easy to splash around will not be formed, which is conducive to avoiding safety hazards. When the chemically strengthened glass-ceramics is used as the cover glass of a display screen, it can also meet emergency use requirements after falling and breaking.
[0229] In some embodiments, the value of the relational expression C may be: 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 0.93, 1.12, 1.00, 0.97, 1.03, 0.99, 1.01, 0.98, 0.92 or 1.06, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0230] In the present application, by making the chemically strengthened microcrystalline glass meet appropriate stress characteristics and / or surface composition characteristics, it is beneficial to obtain chemically strengthened microcrystalline glass products with high stress levels, and then it is beneficial to exert the effect of stress characteristics on improving mechanical strength properties, so that the chemically strengthened microcrystalline glass meets excellent damage resistance and high safety performance.
[0231] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 140.00MPa≤CS_50, preferably, 180.00MPa≤CS_50, and more preferably, 180MPa≤CS_50≤240.00MPa, wherein CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened glass-ceramics.
[0232] In some embodiments, the CS_50 of the chemically strengthened glass-ceramics can be 140.00 MPa, 150.00 MPa, 160.00 MPa, 170.00 MPa, 180.00 MPa, 190.00 MPa, 200.00 MPa, 210.00 MPa, 220.00 MPa, 230.00 MPa, 240.00 MPa, 210.89 MPa, 216.96 MPa, 216.18 MPa, 217.56MPa, 216.54MPa, 214.69MPa, 217.72MPa, 218.14MPa, 216.14MPa, 212.31MPa, 213.77MPa, 215.64MPa, 201.79MPa or 213.58MPa, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained.
[0233] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 90.00 μm ≤ DOL_0, preferably, 100.00 μm ≤ DOL_0, and more preferably, 100.00 μm ≤ DOL_0 ≤ 160.00 μm, wherein DOL_0 is the depth of the compressive stress layer. By making the chemically strengthened glass-ceramics have an appropriate DOL_0, it is possible to prevent the sudden cracks generated when blunt objects or sharp objects impact or pierce, directly penetrating the compressive stress area to reach the tensile stress area, causing the chemically strengthened glass-ceramics to break, thereby being more conducive to improving the energy of the chemically strengthened glass-ceramics to offset the crack propagation, thereby ensuring that the chemically strengthened glass-ceramics has excellent damage resistance, such as excellent drop damage resistance.
[0234] In some embodiments, the DOL_0 of the chemically strengthened glass-ceramics can be 90.00μm, 100.00μm, 105.00μm, 110.00μm, 115.00μm, 120μm, 130μm, 140μm, 150μm, 160μm, 110.04μm, 107.70μm, 109.97μm, 109.32μm, 109.13μm, 109.87μm, 109.42μm, 110.63μm, 109.11μm, 108.94μm, 111.27μm, 106.65μm or 119.97μm, or can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the chemically strengthened glass-ceramics having the desired properties of the present application can be obtained.
[0235] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 0.18≤DOL_0 / t, preferably, 0.20≤DOL_0 / t≤0.25, and more preferably, 0.22≤DOL_0 / t≤0.23, wherein DOL_0 is the depth of the compressive stress layer, and t is the thickness of the chemically strengthened glass-ceramics. By making the depth of the compressive stress layer and the thickness of the chemically strengthened glass-ceramics meet an appropriate proportional relationship, it is beneficial to ensure that the chemically strengthened glass-ceramics is in a better stress distribution state, and further facilitate the improvement of the mechanical strength performance of the stress structure.
[0236] In some embodiments, the value of DOL_0 / t in the chemically strengthened glass-ceramics may be 0.20 to 0.23 or 0.21 to 0.22. In some embodiments, the value of DOL_0 / t in the chemically strengthened glass-ceramics may be 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24 or 0.25, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0237] The thickness t of the chemically strengthened glass-ceramics described in the present application is not particularly limited. For example, in some embodiments of the present application, the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics is in the form of a plate. Optionally, the thickness t of the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics can be 0.35 to 1.0 mm; preferably, the thickness t is 0.4 to 0.7 mm; more preferably, the thickness t is 0.45 mm to 0.55 mm. In some embodiments of the present application, the thickness of the chemically strengthened glass-ceramics described in the present application can be 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1.0 mm, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. At present, electronic devices often pursue lightness and thinness, believing that the smaller the thickness, the lighter the weight, and the better the optical effect. The present application can make the chemically strengthened microcrystalline glass product as thin as possible while ensuring the strength, so as to meet the requirements of lightness and thinness of electronic devices.
[0238] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 150MPa≤|CT_CV|, preferably, 150MPa≤|CT_CV|≤250MPa, and more preferably, 180MPa≤|CT_CV|≤250MPa, wherein |CT_CV| is the absolute value of the maximum tensile stress.
[0239] In some embodiments, the |CT_CV| of the chemically strengthened glass-ceramics may be 150.00 MPa to 250.00 MPa, 150.00 MPa to 180.00 MPa, 150.00 MPa to 240.00 MPa, 190.00 MPa to 230.00 MPa, or 200.00 MPa to 230.00 MPa. In some embodiments, the |CT_CV| of the chemically strengthened glass-ceramics can be 150.00MPa, 160.00MPa, 170.00MPa, 180.00MPa, 190.00MPa, 200.00MPa, 210.00MPa, 220.00MPa, 230.00MPa, 240.00MPa, 250.00MPa, 226.68MPa, 193.35MPa, 215.52MPa , 224.35MPa, 209.26MPa, 217.21MPa, 216.52MPa, 222.24MPa, 234.28MPa, 202.79MPa, 201.74MPa, 218.25MPa, 219.42MPa or 207.75MPa, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained.
[0240] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 100.00 MPa≤|CT_AV|, preferably, 100.00 MPa≤|CT_AV|≤160.00 MPa, and more preferably, 130.00 MPa≤|CT_AV|≤160.00 MPa, wherein |CT_AV| is the absolute value of the average tensile stress.
[0241] In some embodiments, the |CT_AV| of the chemically strengthened glass-ceramics may be 100.00MPa to 160.00MPa, 100.00MPa to 125.00MPa, 105.00MPa to 120.00MPa, 100.00MPa to 150.00MPa, or 110.00MPa to 115.00MPa. In some embodiments, the |CT_AV| of the chemically strengthened glass-ceramics may be 100.00MPa, 110.00MPa, 120.00MPa, 125.00MPa, 130.00MPa, 135.00MPa, 140.00MPa, 150.00MPa, 160.00MPa, 145.28MPa, 135.44MPa, 147.26MPa, 142.53MPa , 138.79MPa, 150.24MPa, 144.35MPa, 146.02MPa, 142.02MPa, 139.69MPa, 140.56MPa, 139.63MPa, 142.25MPa or 138.91MPa, or it can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained.
[0242] It should be understood that the "surface composition" in the present application can be the material composition or component distribution of the material composition on the surface of the substrate glass, glass-ceramics or chemically strengthened glass-ceramics, and can also be the mass percentage of a certain component on the surface of the substrate glass, glass-ceramics or chemically strengthened glass-ceramics, the molar percentage of a certain component, the mass percentage relationship between two or more material components, the mass content relationship between two or more material components, the molar content relationship between two or more material components, and a combination of the foregoing, as well as others. For example: the mass percentage of Na2O on the surface of chemically strengthened glass-ceramics or the mass percentage of K2O on the surface of chemically strengthened glass-ceramics, and another example: the mass percentage of Na2O on the surface of chemically strengthened glass-ceramics and the mass percentage of K2O on the surface of chemically strengthened glass-ceramics.
[0243] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: Na2O ≥5.0%, preferably 5.0% to 20%, more preferably 6% to 17%, wherein M Na2O M is the surface of chemically strengthened glass-ceramics Na2O mass percentage.
[0244] In some embodiments, the mass percentage M of Na2O on the surface of the chemically strengthened glass-ceramics is Na2O It can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 16%, 17%, 18%, 19%, 20%, 12.87%, 7.93%, 10.85%, 12.63%, 13.02%, 13.63%, 15.25%, 16.16%, 12.75%, 12.18%, 11.95%, 11.26% or 12.14%, or it can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the required properties of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the chemically strengthened glass-ceramics having the desired properties of the present application can be obtained.
[0245] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: K2O ≤3.0%, preferably 0.2% to 2%, more preferably 0.3% to 1.6%, wherein M K2O is the mass percentage of K2O on the surface of chemically strengthened glass-ceramics.
[0246] In some embodiments, the mass percentage M of K2O on the surface of the chemically strengthened microcrystalline glass is K2O It can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 1.33%, 1.21%, 1.47%, 1.48%, 1.42%, 1.57%, 1.32%, 1.43%, 1.36%, 1.41%, 1.54%, 1.5% or 1.52%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0247] In some embodiments of the present application, after the two main surfaces of the chemically strengthened micro-ceramic glass are thinned by 3 μm, the obtained thinned chemical micro-ceramic glass satisfies: the mass percentage M' of K2O on the surface of the chemical micro-ceramic glass K2O and the mass percentage of Na2O on the surface of chemical glass-ceramics M' Na2O for:
[0248] M'K2O <3.0%, preferably 0.0% to 1%, more preferably 0.1% to 0.5%,
[0249] M' Na2O <15.0%, preferably 3.0% to 14%, more preferably 4% to 12%.
[0250] In some embodiments, M' K2O It can be 0.00%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 0.300%, 0.289%, 0.318%, 0.321%, 0.315%, 0.301%, 0.326%, 0.305%, 0.322%, 0.319% or 0.325%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0251] In some embodiments, M' Na2O It can be 3.00%, 4.00%, 5.00%, 6.00%, 7.00%, 8.00%, 9.00%, 10.00%, 11.00%, 12.00%, 13.00%, 14.00%, 8.40%, 5.03%, 6.78%, 8.31%, 8.86%, 8.81%, 9.02%, 9.55%, 9.71%, 8.36%, 8.07%, 8.01%, 7.83% or 8.08%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0252] It should be understood that the chemically strengthened glass-ceramics of the present application is made of glass-ceramics after chemical strengthening treatment, and the mass percentages of Na2O and K2O on the surface of the chemically strengthened glass-ceramics are different from the mass percentages of Na2O and K2O on the surface of the chemically strengthened glass-ceramics after thinning by 3 μm on both main surfaces of the chemically strengthened glass-ceramics along the thickness direction. This is because ion exchange (for example, Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K +) is replaced, and the surface of the microcrystalline glass is in direct contact with the salt bath, with less obstruction from the glass matrix, and a greater surface exchange rate, forcing larger alkali metal ions (e.g., Na + or K + ) is easier to enter therein, but as the ion exchange proceeds, the internal ions undergo ion exchange, and the higher the resistance encountered by the glass matrix, the more difficult it is to proceed. Therefore, compared with the chemically strengthened microcrystalline glass after the two main surfaces are thinned by 3μm in the thickness direction, the mass percentage of Na2O and K2O on the surface of the thinned chemically strengthened microcrystalline glass is higher than that of the unthinned chemically strengthened microcrystalline glass. It should be understood that the chemically strengthened microcrystalline glass of the present application is made of microcrystalline glass that has been chemically strengthened, and the composition at the center of the chemically strengthened microcrystalline glass is the same or substantially the same as the composition of the microcrystalline glass. Compared with the microcrystalline glass before chemical strengthening treatment, after chemical strengthening treatment, the composition at the surface of the microcrystalline glass product may be different from the composition of the microcrystalline glass before chemical strengthening treatment. This is because ion exchange will occur during the chemical strengthening process. When the ion exchange is performed, a type of alkali metal ion (for example, Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced. However, in an embodiment, the glass composition and phase assembly at or near the depth or thickness center of the microcrystalline glass product will still have the composition and phase assembly of the newly formed microcrystalline glass. That is, in the present application, the composition (e.g., the composition of the tensile stress layer) and phase assembly at the center of the chemically strengthened microcrystalline glass are the same or substantially the same as those of the microcrystalline glass that has not been chemically strengthened.
[0253] In the present application, the glass-ceramics used to prepare chemically strengthened glass-ceramics can be obtained by heat treating a substrate glass. The composition of the substrate glass is the same or substantially the same as that of the glass-ceramics in terms of the molar percentage or mass percentage of the oxide.
[0254] In some embodiments of the present application, the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, in terms of the molar percentage of the oxides, includes: SiO2: 58% to 66%, Al2O3: 0% to 3.5%, P2O5: 1% to 2.5%, ZrO2: 3.5% to 5.5%, Li2O: 22% to 32%, SrO: 0% to 2.5%, Na2O: 0% to 3%. By adjusting and controlling the content range of each oxide component to meet a specific glass composition, it is beneficial to obtain a microcrystalline glass that meets a specific crystal phase structure, and it is beneficial to obtain a chemically strengthened microcrystalline glass that meets a specific stress structure.
[0255] In some embodiments of the present application, the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, measured in molar percentage of oxides, further includes: K2O: 0% to 1%, CaO: 0% to 1.5%, B2O3: 0% to 1%, Ta2O5: 0% to 1%, BaO: 0% to 2.5%.
[0256] It should be understood that the measurement method of the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be transformed by conversion. For example, the above-mentioned measurement method based on the molar percentage of the oxide can be converted into the mass percentage of the oxide.
[0257] In some embodiments of the present application, the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics, in terms of the mass percentage of oxides, includes: SiO2: 60% to 70%, Al2O3: 0% to 6%, P2O5: 2% to 8%, ZrO2: 8% to 12%, Li2O: 10% to 20%, SrO: 0% to 6%, Na2O: 0% to 3%. In some embodiments of the present application, the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics, in terms of the mass percentage of oxides, further includes: K2O: 0% to 2%, CaO: 0% to 2%, B2O3: 0% to 1%, Ta2O5: 0% to 2%, BaO: 0% to 6%.
[0258] In the present application, SiO2 is a glass network forming body oxide, which is an indispensable component of the glass network structure. At the same time, SiO2 is also an important component of the main crystalline phase lithium disilicate (Li2Si2O5) crystalline phase. Properly increasing the content of SiO2 can increase the stability and mechanical strength of the glass, which is conducive to ensuring the precipitation of the desired content of lithium disilicate crystalline phase, but excessive SiO2 will increase the viscosity of the substrate glass, making the glass melting more difficult, thereby reducing the formability of the substrate glass. Therefore, in order to meet the glass formability requirements and achieve the desired crystallization effect of the present application, and then obtain the desired microcrystalline glass or chemically strengthened microcrystalline glass products of the present application, in the present application, the molar percentage content of SiO2 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 58% to 66%, or the mass percentage content of SiO2 is 60% to 70%.
[0259] In some embodiments, the molar percentage of SiO2 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 58% to 66%, 60% to 65%, 60.5% to 64.5%, or 60.5% to 63% in terms of the molar percentage of oxides. In some embodiments, the molar percentage of SiO2 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 60.94%, 61.15%, 61.22%, 61.43%, 61.72%, or 62.22% in terms of the molar percentage of oxides, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0260] In some embodiments, the mass percentage of SiO2 in the composition of the substrate glass, the composition of the microcrystalline glass, or the composition at the center of the chemically strengthened microcrystalline glass, measured as a mass percentage of the oxide, may be 60% to 70%, 62% to 68%, 63% to 67%, or 63% to 66.5%. In some embodiments, in terms of the mass percentage of oxide, the mass percentage of SiO2 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 65.92%, 66.06%, 63.98%, 63.44%, 63.31%, 64.45%, 65.72%, 65.54% or 63.87%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0261] In the present application, Al2O3 is an optional component, and the addition of an appropriate amount of Al2O3 helps to promote the exchange of ions during the chemical strengthening process to a certain extent. However, excessive Al2O3 will increase the viscosity of the glass and easily lead to the precipitation of other crystalline phases, such as petalite, which affects the crystalline structure of the microcrystalline glass. Therefore, in the present application, in order to meet the desired crystalline structure and enable the microcrystalline glass or chemically strengthened microcrystalline glass to obtain the desired performance, the molar percentage content of Al2O3 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 3.5%, or the mass percentage content of Al2O3 is 0% to 6%.
[0262] In some embodiments, the molar percentage of Al2O3 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0% to 3.5%, 1% to 3.5%, 1% to 2.5%, 0% to 2.5%, 0.1% to 2% or 1% to 2%, measured as a molar percentage of the oxide. In some embodiments, in terms of the molar percentage of oxide, the molar percentage of Al2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 3%, 3.5%, 1.22%, 1.37%, 1.38% or 1.4%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0263] In some embodiments, the mass percentage of Al2O3 in the composition of the substrate glass, the composition of the microcrystalline glass, or the composition at the center of the chemically strengthened microcrystalline glass, measured as a mass percentage of the oxide, can be 0% to 6%, 1% to 6%, 2% to 6%, 0% to 5%, 0.1% to 4%, 2% to 3%, or 1.5% to 3.5%. In some embodiments, in terms of the mass percentage of oxide, in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics, the mass percentage of Al2O3 can be 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 2.52%, 2.51%, 2.43%, 2.41%, 2.15%, 2.48% or 2.45%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0264] In the present application, P2O5 is a glass-forming oxide, which exists in the network structure as a phosphorus-oxygen tetrahedron [PO4]. P2O5 appears preferentially during the heat treatment process, first causing the glass to phase-segregate and form an amorphous precursor phase Li3PO4, and then using Li3PO4 as a non-uniform nucleation point, crystalline phases such as lithium silicate grow by adhering to the amorphous Li3PO4. With the increase of the P2O5 content, the number of non-uniform nucleation points increases, and the grains with Li3PO4 as the nucleation point are effectively refined, which is beneficial to improving the overall transmittance of microcrystalline glass, the uniformity of the glass and reducing the b value. However, when the P2O5 content is too much, it is easy to generate more Li3PO4 crystals, so that the Li2O content of lithium silicate is insufficient, which leads to the substrate glass being easy to precipitate quartz crystals, resulting in a decrease in the transmittance of microcrystalline glass and a decrease in the overall optical uniformity of microcrystalline glass. When the P2O5 content is too little, the size of the precipitated crystals is too large, which is easy to cause the glass to lose transparency. Therefore, in order to achieve the desired crystallization effect of the present application and make the microcrystalline glass or chemically strengthened microcrystalline glass obtain the desired performance, the molar percentage content of P2O5 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 1% to 2.5%, or the mass percentage content of P2O5 is 2% to 8%.
[0265] In some embodiments, the molar percentage of P2O5 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 1% to 2.5%, 1% to 2%, 1.2% to 2% or 1.5% to 2%, measured as a molar percentage of the oxide. In some embodiments, in terms of the molar percentage of oxide, the molar percentage of P2O5 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 1.82%, 1.83%, 1.84%, 1.85% or 1.86%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0266] In some embodiments, the mass percentage of P2O5 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 2% to 8%, 3% to 6%, 3% to 5%, or 4% to 4.8% by mass percentage of oxides. In some embodiments, the mass percentage of P2O5 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 4.66%, 4.68%, 4.54%, 4.49%, 4.55%, 4.56%, 4.65%, 4.64%, or 4.52% by mass percentage of oxides, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0267] In the present application, ZrO2 is an intermediate oxide in the formation of glass. An appropriate amount of ZrO2 can improve the chemical stability of glass, increase the hardness of glass, and the scratch and drop resistance of glass. At the same time, due to the high cation charge and strong field strength of ZrO2, it has a greater accumulation effect on the glass structure and is also commonly used as a nucleating agent in microcrystalline glass. In the present invention, the greater the ZrO2 content, the higher the stress of the system, and the more ideal the stress effect produced, but too high ZrO2 will deteriorate the optical properties of microcrystalline glass. Therefore, in order to meet the requirements of glass formability and achieve the strength effect expected in the present application, the molar percentage content of ZrO2 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 3.5% to 5.5%, or the mass percentage content of ZrO2 is 8% to 12%.
[0268] In some embodiments, the molar percentage of ZrO2 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 3.5% to 5.5%, 4% to 5%, 4.2% to 5% or 4% to 4.8% in terms of the molar percentage of the oxide. In some embodiments, the molar percentage of ZrO2 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 3.5%, 4%, 4.5%, 5%, 5.5%, 4.47%, 4.57%, 4.59%, 4.6%, 4.61% or 4.66% in terms of the molar percentage of the oxide, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0269] In some embodiments, the mass percentage of ZrO2 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 8% to 12%, 8% to 11%, 9% to 11%, or 9.2% to 10.5% by mass percentage of oxide. In some embodiments, the mass percentage of ZrO2 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 10.12%, 9.84%, 9.72%, 9.52%, 9.98%, 9.88%, 10.07%, 10.04%, or 9.79% by mass percentage of oxide, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0270] In the present application, Li2O is a necessary component and a network exo-oxide formed by glass. It can not only improve the viscosity of the glass, promote the melting and clarification of the glass liquid, but also is one of the main components for forming lithium disilicate crystals. At the same time, Li2O can also provide alkali metal lithium ions for ion exchange with large radius ions of the molten salt bath, which is an important factor affecting the stress level that can be obtained by chemically strengthened microcrystalline glass. However, excessive Li2O may cause the stability of the glass crystallization process to deteriorate, and even precipitate other undesirable crystalline phases, which deteriorates the optical properties of the microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired crystal phase structure, optical properties and mechanical strength properties, the molar percentage content of Li2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 22% to 32%, or the mass percentage content of Li2O is 10% to 20%.
[0271] In some embodiments, the molar percentage of Li2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 22% to 32%, 23% to 31%, 24% to 30%, 25% to 31%, 27% to 30.5% or 28.5% to 29.8%, calculated as a molar percentage of the oxide. In some embodiments, the molar percentage of Li2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, measured as a molar percentage of the oxide, can be 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 29.25%, 29.38%, 29.39%, 29.4% or 29.52%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0272] In some embodiments, the mass percentage of Li2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, as measured by the mass percentage of the oxide, may be 10% to 20%, 11% to 18%, 12% to 16%, 15% to 16%, 14% to 17%, or 13% to 16.5%. In some embodiments, the mass percentage of Li2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, as measured by the mass percentage of the oxide, may be 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 18.5%, 19%, 19.5%, 20%, 15.49%, 15.71%, 15.28%, 15.09%, 15.11%, 15.47%, 15.33%, 15.63%, 15.59% or 15.19%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0273] In the present application, SrO is an alkaline earth metal oxide as an optional component. An appropriate amount of SrO can play a role in regulating the glass phase composition in microcrystalline glass, which helps to increase the density of microcrystalline glass and increase its Young's modulus. At the same time, it is also beneficial to reduce the thermal expansion softening point of microcrystalline glass, which is beneficial for hot bending of microcrystalline glass into 3D curved microcrystalline glass. However, excessive SrO will deteriorate the optical properties of microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage of SrO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 2.5%, or the mass percentage of SrO is 0% to 6%.
[0274] In some embodiments, the mole percentage of SrO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0% to 2.5%, 0% to 2%, or 0% to 1.9% by mole percentage of oxide. In some embodiments, the mole percentage of SrO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 1.38%, or 1.83% by mole percentage of oxide, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0275] In some embodiments, the mass percentage of SrO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 2.52% or 3.33%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0276] In the present application, Na2O is an optional component and a network exosome oxide. An appropriate amount of Na2O can provide free oxygen, improve the viscosity of the glass, promote the melting and clarification of the glass liquid, and adjust the chemical strengthening rate. However, excessive Na2O will not only reduce the crystallinity of the microcrystalline glass, but also affect the chemical strengthening effect. Therefore, in order to ensure that the microcrystalline glass or chemically strengthened microcrystalline glass meets the desired structure and obtains the desired performance, the molar percentage content of Na2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 3%, or the mass percentage content of Na2O is 0% to 3%.
[0277] In some embodiments, the molar percentage of Na2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0% to 3%, 0% to 2.6% or 0% to 1% by molar percentage of the oxide. In some embodiments, in terms of the molar percentage of oxide, the molar percentage of Na2O in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.5%, 2.6%, 3% or 0.46%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0278] In some embodiments, in terms of the mass percentage of oxide, in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics, the mass percentage of Na2O can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.5%, 2.6%, 3% or 0.51%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0279] In the present application, K2O is an oxide outside the glass network and is one of the optional components. An appropriate amount of K2O can provide free oxygen to increase the oxygen-silicon ratio in the glass structure, but too much K2O will affect the network structure of the glass, and affect the optical properties, thermal stability, chemical stability, mechanical strength and weather resistance of the glass. Therefore, in order to ensure that the microcrystalline glass or chemically strengthened microcrystalline glass meets the desired structure and obtains the desired performance, the molar percentage content of K2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 1%, or the mass percentage content of K2O is 0% to 2%.
[0280] In some embodiments, the molar percentage of K2O in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or 0.46% in terms of the molar percentage of the oxide, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0281] In some embodiments, the mass percentage of K2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2% or 0.77%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0282] In the present application, CaO is an optional component of the network outer oxide formed by glass. An appropriate amount of CaO helps to reduce the high temperature viscosity of the glass and increase the density of the glass, but an excessive amount of CaO will shorten the material properties of the glass and increase its brittleness. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage content of CaO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 1.5%, or the mass percentage content of CaO is 0% to 2%.
[0283] In some embodiments, in terms of the molar percentage of oxide, the molar percentage of CaO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 0.95% or 0.92%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0284] In some embodiments, in terms of the mass percentage of oxide, in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics, the mass percentage of CaO can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 0.95% or 0.92%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0285] In the present application, B2O3 is an optional component, and an appropriate amount of B2O3 can be used as a flux and / or softener to help improve the molding and hot bending effects of the glass, but excessive B2O3 will cause the crystallization process to be uncontrollable, resulting in the deterioration of the optical properties of the microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage content of B2O3 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 1%, or the mass percentage content of B2O3 is 0% to 1%.
[0286] In some embodiments, the molar percentage of B2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or 0.46% in terms of the molar percentage of the oxide, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0287] In some embodiments, in terms of the mass percentage of oxide, the mass percentage of B2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or 0.56%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0288] In the present application, the selective addition of an appropriate amount of Ta2O5 helps to increase the density of the glass-ceramics and increase its Young's modulus, but it may also increase the refractive index of the glass-ceramics and reduce the optical properties of the glass-ceramics. Therefore, in order to obtain glass-ceramics or chemically strengthened glass-ceramics that meet the desired optical properties and mechanical strength properties, the molar percentage content of Ta2O5 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics is 0% to 1%, or the mass percentage content of Ta2O5 is 0% to 2%.
[0289] In some embodiments, the molar percentage of Ta2O5 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 0.46% or 1%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0290] In some embodiments, the mass percentage of Ta2O5 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.2%, 1.5%, 1.8%, 2%, 1.3% or 1%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0291] In the present application, BaO is an optional component and is an alkaline earth metal oxide. An appropriate amount of BaO can play a role in regulating the glass phase composition in microcrystalline glass, which helps to increase the density of microcrystalline glass and increase its Young's modulus. However, excessive BaO will deteriorate the optical properties of microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage content of BaO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 2.5%, or the mass percentage content of BaO is 0% to 6%.
[0292] In some embodiments, in terms of the molar percentage of oxide, the molar percentage of BaO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.9%, 2%, 2.5%, 1.37%, 1.38% or 1.83%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0293] In some embodiments, in terms of the mass percentage of oxide, the mass percentage of BaO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 3.65%, 3.68% or 4.85%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0294] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 2.00≤n(SiO2) / n(Li2O)≤2.40, preferably, 2.00≤n(SiO2) / n(Li2O)≤2.30, and more preferably, 2.02≤n(SiO2) / n(Li2O)≤2.20, wherein n(SiO2) is the molar percentage content of SiO2 at the center of the chemically strengthened glass-ceramics, and n(Li2O) is the molar percentage content of Li2O at the center of the chemically strengthened glass-ceramics. It should be noted that in the present application, the content relationship formula for each oxide is substituted into each formula in terms of the content percentage of the oxide mole, and the molar unit does not participate in the calculation of the formula. By adjusting the content of each oxide to satisfy a specific content relationship, it is beneficial to obtain a glass-ceramic or chemically strengthened glass-ceramics that meets the desired mechanical strength properties.
[0295] In some embodiments, the value of n(SiO2) / n(Li2O) may be 2, 2.1, 2.2, 2.3, 2.4, 2.08, 2.09 or 2.12, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0296] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 90%≤n(SiO2)+n(Li2O)≤95%, preferably, 90%≤n(SiO2)+n(Li2O)≤92%, wherein n(SiO2) is the molar percentage content of SiO2 at the center of the chemically strengthened glass-ceramics, and n(Li2O) is the molar percentage content of Li2O at the center of the chemically strengthened glass-ceramics. It should be noted that the content relationship formulas for each oxide in the present application are substituted into each formula based on the content percentage of the oxide mole, and the molar unit does not participate in the calculation of the formula. By adjusting the content of each oxide to satisfy a specific content relationship, it is beneficial to obtain a glass-ceramic or chemically strengthened glass-ceramics that meets the desired mechanical strength properties.
[0297] In some embodiments, the value of n(SiO2)+n(Li2O) may be 90%, 91%, 92%, 93%, 94%, 95%, 90.19%, 90.4%, 90.62%, 90.82%, 91.24% or 91.62%, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0298] In the present application, by adjusting and controlling the content relationship of SiO2 and Li2O, it is beneficial to ensure that a microcrystalline glass that meets the desired performance and has lithium disilicate as the main crystal phase structure is obtained, and it is also beneficial to achieve the desired stress distribution structure.
[0299] In the present application, "lithium disilicate crystalline phase has a higher mass percentage than other crystalline phases present in chemically strengthened glass-ceramics" or "lithium disilicate is the main crystalline phase" or other similar expressions refer to that the mass of lithium disilicate crystalline phase accounts for more than 80 mass percent (mass % or wt %) of all crystalline phases of glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics according to the embodiments of the present application. In some embodiments of the present application, in the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, the mass of lithium disilicate crystalline phase accounts for 80wt% to 100wt% of all crystalline phases, preferably, in all crystalline phases of glass-ceramics or chemically strengthened glass-ceramics, the mass of lithium disilicate crystalline phase accounts for 85wt% to 100wt%. In some embodiments, in all crystalline phases of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, the mass proportion of the lithium disilicate crystalline phase can be 80wt%, 80.5wt%, 81wt%, 81.5wt%, 82wt%, 82.5wt%, 83wt%, 83.5wt%, 84wt%, 84.5wt%, 85wt%, 85.5wt%, 86wt%, 86.5wt%, 87wt%, 87.5wt%, 88wt%, 88.5wt%, 89wt%, 89.5wt%, 90wt%, 95wt% or 100wt%, or it can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0300] In the present application, the crystallinity of the glass-ceramics used to prepare chemically strengthened glass-ceramics does not change significantly after chemical strengthening treatment to obtain chemically strengthened glass-ceramics, and the crystallinity of the glass-ceramics is similar to or basically the same as that of the chemically strengthened glass-ceramics.
[0301] In some embodiments of the present application, the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics is not less than 60%, preferably, the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics is 70% to 90%, and more preferably, the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics is 70% to 80%. The higher the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, the more conducive it is to obtain high mechanical strength properties and high damage resistance. However, if the crystallinity is too high, it is easy to affect the chemical strengthening effect of the glass-ceramics, resulting in an extension of the chemical strengthening time for preparing chemically strengthened glass-ceramics with a high stress level, and it is also easy to affect the optical properties of the glass-ceramics. In the present application, by making the glass-ceramics meet the desired crystallinity, it is conducive to making the chemically strengthened glass-ceramics prepared also meet the desired crystallinity, and it is more conducive to obtaining chemically strengthened glass-ceramics that meet the desired high mechanical strength properties, high damage resistance and excellent optical properties.
[0302] In some embodiments, the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics can be 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 76.7%, 76.6%, 70.89%, 70.69%, 73.77%, 70.4%, 75.45%, 75.61%, 71.32% or 72.29%, or it can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0303] In some embodiments of the present application, in the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, the average grain size does not exceed 50 nm, preferably, the average grain size is 10 nm to 40 nm, and more preferably, the average grain size is 15 to 30 nm. The appropriate average grain size is conducive to the glass-ceramics having both excellent optical properties and high intrinsic strength, and if the average grain size is too high, the glass-ceramics is prone to devitrification. In the present application, by making the glass-ceramics or chemically strengthened glass-ceramics meet the appropriate average grain size, it is conducive to ensuring that the glass-ceramics or chemically strengthened glass-ceramics achieve excellent mechanical strength properties and excellent optical properties.
[0304] In some embodiments, the average grain size of the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics can be 50nm, 40nm, 35nm, 30nm, 25nm, 20nm, 15nm, 10nm, 22.8nm, 23.0nm, 26.4nm, 23.3nm, 25.6nm, 24.3nm, 24.1nm or 26.0nm, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0305] In some embodiments of the present application, in the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, non-limiting examples of other possible crystalline phases include: petalite crystalline phase, and / or, lithium phosphate crystalline phase. In some embodiments, the mass percentage of the petalite crystalline phase contained in the glass-ceramics or chemically strengthened glass-ceramics is less than or equal to 10%, preferably, the mass percentage of the petalite crystalline phase in the glass-ceramics or chemically strengthened glass-ceramics is less than or equal to 5%, and more preferably, the glass-ceramics or chemically strengthened glass-ceramics do not contain petalite crystalline phase. By controlling the precipitation of other crystalline phases (such as petalite crystalline phase), it is more conducive to ensuring that the lithium disilicate crystalline phase forms a desired interlocking structure, thereby ensuring that the glass-ceramics or chemically strengthened glass-ceramics obtain high mechanical strength properties, excellent optical properties and excellent damage resistance.
[0306] In some embodiments of the present application, when the thickness does not exceed 0.70 mm, the b value of the glass-ceramic or chemically strengthened glass-ceramic used to prepare the chemically strengthened glass-ceramic is less than 1.0, preferably, the b value is less than 0.80, and more preferably, the b value is ≤ 0.60. It should be understood that in the present application, after the glass-ceramic is chemically strengthened to obtain the chemically strengthened glass-ceramic, its optical properties will not change significantly, that is, the b value, transmittance, etc. of the glass-ceramic are similar to or substantially the same as the b value, transmittance, etc. of the chemically strengthened glass-ceramic. In the present application, the b value refers to the optical b value measured under the D65 light source. The present application uses Konica Minolta CM-3600A to test the b value in transmittance mode, and b(D65) is shown in the result. The smaller the b value, the better the display effect of the glass-ceramic can be ensured. When the b value is too large, the glass-ceramic will have an unexpected color, resulting in its display effect failing to meet the application requirements of the display cover glass.
[0307] In some embodiments, the b value of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics can be 1.0, 0.9, 0.8, 0.70, 0.65, 0.60, 0.55, 0.50, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.56, 0.54, 0.52, 0.44, 0.42, 0.47 or 0.41, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0308] In some embodiments of the present application, the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics are transparent in the visible light wavelength range. Preferably, for light with a wavelength of 550nm, the transmittance of the chemically strengthened glass-ceramics is ≥85%, preferably, the transmittance is ≥90%, and more preferably, the transmittance is ≥90.2%. Chemically strengthened glass-ceramics that meet this transmittance can ensure good light transmittance and good transparency, and are suitable for use in display screens that require display effects. The "visible light wavelength range" here refers to light with a wavelength of 360nm-740nm.
[0309] In some embodiments, for 550nm wavelength light, the transmittance of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics can be 85%, 90%, 90.2%, 91%, 92%, 90.4%, 90.46%, 90.32%, 90.22%, 90.27%, 90.51%, 90.35%, 90.71%, 90.63%, 90.52%, 90.46% or 90.32%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0310] In some embodiments of the present application, the Young's modulus of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics is not less than 100 GPa, preferably, the Young's modulus is not less than 110 GPa, more preferably, the Young's modulus is 110 GPa to 130 GPa, and more preferably, the Young's modulus is 114 GPa to 125 GPa. It should be understood that in the present application, after the glass-ceramics is chemically strengthened to obtain chemically strengthened glass-ceramics, its Young's modulus will not decrease, that is, when the Young's modulus of the glass-ceramics is greater than 100 GPa, the Young's modulus of the chemically strengthened glass-ceramics obtained should also be greater than 100 GPa. A higher Young's modulus is conducive to ensuring that the chemically strengthened glass-ceramics has high mechanical strength and high damage resistance.
[0311] In some embodiments, the Young's modulus of the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics can be 100 GPa, 101 GPa, 102 GPa, 103 GPa, 104 GPa, 105 GPa, 106 GPa, 107 GPa, 108 GPa, 109 GPa, 110 GPa, 111 GPa, 112 GPa, 113 GPa, 114 GPa, 115 GPa, 116 GPa, 117 GPa, 118 GPa, 119 GPa, 120 GPa, 125 GPa , 128GPa, 130GPa, 117.07GPa, 114.27GPa, 120.20GPa, 122.40GPa, 120.00GPa, 116.22GPa, 118.95GPa, 114.61GPa, 114.88GPa, 118.63GPa, 114.27GPa or 120.20GPa, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline or chemically strengthened microcrystalline of the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline or chemically strengthened microcrystalline of the performance required by the present application can be obtained.
[0312] In some embodiments of the present application, the Vickers hardness of the chemically strengthened glass-ceramics is ≥700 kgf / mm 2 , preferably, the Vickers hardness is 700kgf / mm 2 ~850kgf / mm 2 The higher Vickers hardness helps ensure that the chemically strengthened glass-ceramics has high mechanical strength and high damage resistance.
[0313] In some embodiments, the Vickers hardness of the chemically strengthened glass-ceramics may be 700 kgf / mm 2 、710kgf / mm2 、720kgf / mm 2 、730kgf / mm 2 、740kgf / mm 2 、750kgf / mm 2 、760kgf / mm 2 、770kgf / mm 2 、780kgf / mm 2 、790kgf / mm 2 、800kgf / mm 2 、810kgf / mm 2 、820kgf / mm 2 、830kgf / mm 2 、840kgf / mm 2 or 850kgf / mm 2 , or it can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0314] In some embodiments of the present application, the density of the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics is not less than 2.54 g / cm 3 , preferably, the density is 2.54 g / cm 3 ~2.64g / cm 3 In some embodiments, the density of the glass-ceramics used to prepare the chemically strengthened glass-ceramics or the chemically strengthened glass-ceramics can be 2.54 g / cm 3 , 2.55g / cm 3 , 2.56g / cm 3 , 2.57g / cm 3 , 2.58g / cm 3 , 2.59g / cm 3 , 2.60g / cm 3 , 2.61g / cm 3 , 2.62g / cm 3 , 2.63g / cm 3 or 2.64 g / cm 3, or it can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the performance required by the present application can be obtained.
[0315] In some embodiments of the present application, the refractive index of the glass-ceramic or chemically strengthened glass-ceramic used to prepare the chemically strengthened glass-ceramic is ≤1.60, preferably, the refractive index is 1.55-1.60. In some embodiments, the refractive index of the glass-ceramic or chemically strengthened glass-ceramic used to prepare the chemically strengthened glass-ceramic can be 1.55, 1.56, 1.57, 1.58, 1.59 or 1.60, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramic or chemically strengthened glass-ceramic with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramic or chemically strengthened glass-ceramic with the required performance of the present application can be obtained.
[0316] In some embodiments of the present application, the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics are 2D, 2.5D, 3D or special-shaped. In some embodiments of the present application, the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics are of equal thickness or unequal thickness. Those skilled in the art can choose according to demand. The "unequal thickness" here refers to the glass-ceramics or chemically strengthened glass-ceramics containing at least two parts with different thicknesses.
[0317] In some embodiments of the present application, a sandpaper drop resistance test is performed on the chemically strengthened glass-ceramics, and the sandpaper used is 80-mesh sandpaper. When the thickness does not exceed 0.70 mm, preferably when the thickness is 0.4 mm to 0.7 mm, and more preferably when the thickness is 0.45 mm to 0.55 mm, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥ 1.60 m, and preferably, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is 1.65 m to 2.50 m. The larger the measured average sandpaper drop resistance height value, the better the drop damage resistance of the chemically strengthened glass-ceramics.
[0318] In some embodiments, when the chemically strengthened glass-ceramics is dropped on 80-grit sandpaper, the average sandpaper drop height can be 1.60m, 1.65m, 1.7m, 1.75m, 1.8m, 1.85m, 1.9m, 1.95m, 2m, 2.1m, 2.2m, 2.3m, 2.4m, 2.5m, 1.79m, 1.67m, 1.82m, 1.76m or 1.72m, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0319] In some embodiments of the present application, a 10 mm diameter round-head metal pressure rod is used to squeeze the chemically strengthened glass-ceramics, and the single-rod static pressure strength that the chemically strengthened glass-ceramics can withstand is tested. The average value of the single-rod static pressure strength that the chemically strengthened glass-ceramics can withstand is greater than 200 N, preferably greater than 230 N. The larger the measured single-rod static pressure strength that can be sustained, the better the anti-extrusion damage performance of the chemically strengthened glass-ceramics.
[0320] After introducing the composition, crystal phase structure and stress structure of chemically strengthened microcrystalline glass, the preparation method of chemically strengthened microcrystalline glass is introduced in detail below.
[0321] In the present application, the preparation process of chemically strengthened microcrystalline glass mainly includes: the preparation process of microcrystalline glass and the chemical strengthening treatment process, and the preparation process of microcrystalline glass mainly includes: the preparation process of substrate glass and the heat treatment process of substrate glass.
[0322] In the present application, the substrate glass can be prepared by a molding method in the prior art, and the present application has no limitation on this. For example, the molding method of the substrate glass can include but is not limited to float, overflow, rolling or casting processes. For example, the substrate glass can be obtained by uniformly mixing the components according to the formula, melting and molding, cooling and annealing.
[0323] Exemplarily, each raw material (industrial conventional raw material) is configured according to the formula ratio, a clarifier is added, and then mixed for a period of time to obtain a uniform raw material mixture. The raw material mixture is placed in a platinum crucible, a platinum rhodium crucible or a furnace, heated to 1450°C to 1700°C, preferably kept warm for 5 hours or more under the melting temperature condition, and then poured into a molding mold for cooling and molding, preferably cooled to about 900°C, and then placed in an annealing furnace for annealing treatment, preferably the annealing temperature is 450°C to 650°C, and the annealing time is preferably 10 to 48 hours, and then cooled to room temperature with the furnace to obtain the substrate glass. Those skilled in the art can select the type and amount of clarifier according to demand, and they do not need to pay creative labor. Further, the clarifier may include but is not limited to one or more of sodium chloride, tin oxide, antimony oxide or arsenic oxide, and the amount of clarifier added may be 0-1wt% of the total amount of each raw material.
[0324] In some embodiments of the present application, the heat treatment process of the substrate glass may include a nucleation treatment and / or a crystallization treatment, preferably a nucleation treatment and a crystallization treatment. In some embodiments, the crystallization treatment includes a one-step crystallization treatment or a two-step crystallization treatment. In some embodiments, in order to prepare curved microcrystalline glass, a two-step crystallization treatment method can be selected. When a two-step crystallization treatment is adopted, the second step crystallization treatment is to heat the crystallized glass raw material obtained by the first step crystallization treatment to a hot pressing temperature, and simultaneously perform a 3D hot bending forming treatment and a second step crystallization treatment. The "crystallized glass raw material" here refers to a glass material with a certain degree of crystallinity, but has not yet reached the crystallinity requirement required for the final sample.
[0325] In some embodiments of the present application, in order to obtain the desired physical and chemical properties of the microcrystalline glass, when the substrate glass is heat treated, a one-step heat treatment may be performed, or two-step or more-step heat treatment may be performed. If a one-step heat treatment is performed, it means that a nucleation treatment (i.e., nucleation treatment) is not performed separately, and a one-step heating is performed directly, and nucleation and crystal growth are performed at a temperature reached in the one-step heating process, which can be understood as a direct crystallization treatment. If a two-step heat treatment is performed, it means that a two-step heating process is performed, including but not limited to the following methods, a first step of nucleation treatment, and a second step of crystallization treatment.
[0326] In some embodiments of the present application, in order to precipitate the desired target crystalline phase in the microcrystalline glass and obtain the desired physical and chemical properties, the substrate glass is subjected to nucleation treatment and crystallization treatment in sequence. Furthermore, when performing the nucleation treatment, the nucleation temperature can be 500-700°C, and the nucleation time can be 10-1440 min; when performing the crystallization treatment, the crystallization temperature can be 600-800°C, and the crystallization time can be 5-1440 min. During the heat treatment process of the nucleation treatment and the crystallization treatment, it is preferred to control the heating rate to be 5-20°C / min, more preferably the heating rate to be 10°C / min, and the cooling rate can be 0.1°C / min-3°C / min.
[0327] In the present application, after heat treatment, the technicians in this field may also perform other conventional steps to obtain a microcrystalline glass sample that meets the required specifications or requirements, for example, shaping treatment, cutting treatment (such as cutting using a multi-wire cutting machine), CNC machining (computer numerical control, i.e., CNC machine tools), thinning treatment or polishing treatment and the like.
[0328] In some embodiments of the present application, chemically strengthened glass-ceramics that meet desired properties can be prepared by subjecting the aforementioned glass-ceramics to a specific chemical strengthening treatment.
[0329] In some embodiments of the present application, the step of polishing and thinning the prepared chemically strengthened glass-ceramics is also included.
[0330] In the present application, the chemical strengthening treatment, namely the ion exchange method, is performed by immersing the microcrystalline glass in a molten salt bath so that the alkali metal ions with smaller ion radius in the microcrystalline glass are exchanged with the alkali metal ions with larger ion radius in the molten salt bath, thereby forming a compressive stress layer on the surface of the microcrystalline glass and a tensile stress layer inside the microcrystalline glass, thereby obtaining chemically strengthened microcrystalline glass with better mechanical properties.
[0331] In some embodiments of the present application, the chemical strengthening treatment may adopt a single-step strengthening method or a multi-step strengthening method. The molten salt bath for chemical strengthening treatment is a molten salt bath containing sodium salt and / or potassium salt. Preferably, the molten salt bath of the present application is a mixed molten salt bath containing sodium salt and potassium salt, and the temperature of the molten salt bath is preferably 380°C to 600°C, preferably 430°C to 550°C. In some embodiments of the present application, the concentration of potassium salt in the salt bath is preferably 60wt% to 95wt%, and the concentration of sodium salt is 5wt% to 40wt%, and more preferably a certain amount (e.g., 0.01wt%-0.3wt%) of lithium salt is added to the salt bath. In some embodiments of the present application, the time of chemical strengthening treatment is preferably 0.1 to 24h. Among them, the sodium salt can be selected from at least one of sodium nitrate, sodium sulfate, and sodium carbonate, preferably sodium nitrate; the potassium salt can be selected from at least one of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate; the lithium salt can be selected from at least one of lithium nitrate, lithium sulfate, and lithium carbonate, preferably lithium nitrate.
[0332] In the present application, the stress distribution structure of the chemically strengthened glass-ceramics is closely related to the glass-ceramics composition (including oxide composition, crystal phase composition), salt bath composition, salt bath temperature and chemical strengthening treatment time. Only when the glass-ceramics of a specific composition is in a suitable salt bath (suitable composition and suitable temperature) and chemically strengthened for a suitable time, can the prepared chemically strengthened glass-ceramics obtain a specific stress distribution structure, thereby achieving the excellent effect expected to be achieved in the present application.
[0333] The chemically strengthened microcrystalline glass with excellent performance provided in the present application can be used in electronic devices, including but not limited to mobile phones, tablet computers, handheld game consoles, portable digital devices (such as digital cameras), vehicle-mounted central control, electronic whiteboard glass, smart home, smart wear (such as smart bracelets, smart watches, smart glasses), and can also be used in vehicles, aircraft or aircraft, and can also be used in any glass device of chemically strengthened microcrystalline glass required. For example, it can be used for display screens, cover glass, touch screens, glass inner screens or inner frames of electronic devices; for example, it can be used for windshields of vehicles, aircraft or aircraft, such as front windshields or side windshields. For example, it can be used for work surfaces, other surfaces, appliance doors, floor tiles, wall panels or storage containers. Other surfaces can include but are not limited to exterior wall surfaces, stair tread surfaces, column veneers or counter surfaces, etc., and storage containers can include but are not limited to cups, plates, medicine bottles or beverage bottles, etc.
[0334] For example, the chemically strengthened glass-ceramics with excellent performance provided in the present application can be used to manufacture glass devices. The glass devices referred to here can be regular or irregular, and those skilled in the art can manufacture them according to requirements.
[0335] For example, the chemically strengthened microcrystalline glass with excellent performance provided by the present application can be used to manufacture cover glass, and the cover glass can be a display cover, back cover or camera protection cover of an electronic device. For example, the chemically strengthened microcrystalline glass with excellent performance provided by the present application can be used in electronic devices. Fig.12 , Fig.13 , Fig.14 and Fig.15 In an embodiment of the present application, an electronic device is provided, which may be an electronic product such as a mobile phone, a tablet computer, a smart wearable device, etc. The electronic device includes a housing 1 assembled on the outside of the electronic device, and components such as a circuit board and a battery located inside the housing 1. The housing 1 includes a display screen cover 11 assembled on the front side and a back cover 12 assembled on the back side. The display screen cover 11 is covered on the display module 4, wherein the display screen cover 11 and / or the back cover 12 are made of the aforementioned chemically strengthened microcrystalline glass. In an embodiment of the present application, the display screen cover 11 and the back cover 12 may all be made of the aforementioned chemically strengthened microcrystalline glass, or only partially made of the aforementioned chemically strengthened microcrystalline glass. In an embodiment of the present application, the display screen may be a touch display screen, and the display screen cover 11 may be a protective cover provided on the touch display screen. In an embodiment of the present application, the back cover 12 may only cover the back side (and the side away from the display screen) of the electronic device, or may cover the back side and side frame of the electronic device at the same time. Optionally, the back cover 12 may cover all side frames around the electronic device, or may cover part of the side frame.
[0336] In some implementation modes of the present application, Fig.13 As shown, the electronic device also includes a camera assembly 2 located inside the housing 1, and the housing 1 may include a camera protection cover 13, which is covered on the camera assembly 2 to protect the camera assembly 2, and the camera protection cover 13 adopts the aforementioned chemically strengthened microcrystalline glass. In the embodiment of the present application, the camera protection cover 13 may be partially made of the aforementioned chemically strengthened microcrystalline glass, or it may be entirely made of the aforementioned chemically strengthened microcrystalline glass. In the embodiment of the present application, the setting position of the camera protection cover 13 is determined according to the setting position of the camera assembly 2, and it may be located on the front side of the electronic device, or it may be located on the back side of the electronic device. In some embodiments of the present application, the camera protection cover 13 may be a separate structure from the display screen cover 11 or the back cover 12. In other embodiments of the present application, the camera protection cover 13 may also be an integrated structure with the display screen cover 11 or the back cover 12.
[0337] In some embodiments of the present application, Fig.14 As shown, the electronic device further includes a middle frame 3 located between the display module 4 and the housing 1 , and the middle frame 3 may include the aforementioned chemically strengthened microcrystalline glass.
[0338] In the embodiments of the present application, the display screen cover, back cover, camera protection cover, and middle frame in the electronic device may be made of any one of the aforementioned chemically strengthened microcrystalline glass, or any two of them may be made of the aforementioned chemically strengthened microcrystalline glass, or all three may be made of the aforementioned chemically strengthened microcrystalline glass, or all four may be made of the aforementioned chemically strengthened microcrystalline glass.
[0339] In some embodiments of the present application, the display screen cover, back cover, camera protection cover or middle frame in the electronic device may be 2D, 2.5D, 3D or special-shaped. In some embodiments of the present application, the display screen cover, back cover, camera protection cover or middle frame in the electronic device may be of equal thickness or unequal thickness.
[0340] The technical solution of the present application is further described in detail below in conjunction with the embodiments. The embodiments of the present application described in detail below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0341] Example 1
[0342] 1. Preparation of substrate glass
[0343] The raw materials were configured according to the proportions of the oxides in Table 1. The total mass of the configured raw materials was 1000 g. 5 g of clarifier sodium chloride (NaCl) was added to the configured raw materials. The mixture was then mixed at a speed of 25 r / min for more than 30 minutes using a V-type mixer to obtain a uniform raw material mixture.
[0344] The mixed raw material mixture is transferred to a platinum crucible, and then melted in a platinum-rhodium crucible at 1600℃ for more than 5 hours, and then poured into a molding mold for molding and cooling. When it cools to about 900℃, it is then placed in a 460℃ annealing furnace for annealing for 12 hours, and then cooled to room temperature with the furnace to obtain a base glass brick with a size of approximately 180mm*65mm*24mm.
[0345] 2. Preparation of glass-ceramics
[0346] The base glass brick is subjected to nucleation treatment and crystallization treatment in sequence to prepare a transparent micro-ceramic glass brick. The composition of the prepared micro-ceramic glass is the same as that of the base glass in terms of the molar percentage of oxides, as shown in Table 1.
[0347] In order to obtain the microcrystalline glass product of Example 1 of the present application, during the nucleation treatment, the temperature is increased to the nucleation temperature at a heating rate of 10°C / min, the nucleation temperature is 520°C, and the nucleation insulation time is 240min; during the crystallization treatment, the temperature is increased from the nucleation temperature to the crystallization temperature at a heating rate of 10°C / min, the crystallization temperature is 710°C, and the crystallization insulation time is 60min, and then the temperature is cooled to room temperature at a cooling rate of 1°C / min, and the microcrystalline glass sample brick can be obtained. The nucleation insulation time here, that is, the nucleation time, refers to the insulation time after the crystallization furnace is heated to the set nucleation temperature at the set heating rate. The crystallization insulation time here, that is, the crystallization time, refers to the insulation time after the crystallization furnace is heated to the set crystallization temperature at the set heating rate.
[0348] The obtained microcrystalline glass sample bricks are cut, CNC processed (the CNC instrument model used in this application is: RCG500S), and polished in turn through cold processing to produce microcrystalline glass samples that meet the required specifications and requirements.
[0349] In the specific examples and comparative examples of the present application, the glass-ceramic sample bricks were subjected to the aforementioned cold working treatment to produce glass-ceramic polished sheet samples with a length and width of 50 mm×50 mm and a thickness of 0.47 mm to 0.54 mm. The thickness of the glass-ceramic polished sheet sample prepared in Example 1 was 0.50 mm.
[0350] The results of testing the glass-ceramics samples obtained in Example 1 are as follows:
[0351] The crystal phase composition, crystallinity, average crystal size (average grain size), expansion softening point, density, refractive index, Young's modulus, optical b value and transmittance (under 550nm wavelength light) of the microcrystalline glass samples were tested respectively. The results are shown in Table 2.
[0352] 3. Preparation of chemically strengthened glass-ceramics
[0353] The microcrystalline glass polishing sheet obtained above was subjected to a one-step chemical strengthening treatment in a mixed salt at 470°C for 450 minutes. The composition of the mixed salt was: 19.99wt% NaNO3+79.98wt% KNO3+0.03wt% LiNO3.
[0354] After the chemical strengthening treatment, the microcrystalline glass sample is taken out and placed on the strengthening furnace body to slowly cool to room temperature, and then the salt wrapped on the surface of the microcrystalline glass is washed off with clean water. After the microcrystalline glass sample is dried, chemically strengthened microcrystalline glass can be obtained.
[0355] The chemically strengthened glass-ceramics obtained in Example 1 were tested as follows:
[0356] Ⅰ. Stress test: The chemically strengthened microcrystalline glass is placed in an SLP-2000 stress meter (the light source wavelength used is 518 nm, SOC=25.5 (nm / cm) / MPa, the refractive index is set according to the refractive index value of the sample to be tested, and the exposure time is 300 μsec) to measure CS_50, DOL_0, |CT_CV|, |CT_AV|; then the tensile stress line density CT_LD value and the relationship A (the CT_LD value minus the ratio of the stress integral of the tensile stress layer from 2 times DOL_0 from the main surface of the chemically strengthened microcrystalline glass to half the thickness of the chemically strengthened microcrystalline glass to the thickness t) and the value of the relationship C (CS_50 / |CT_CV|) are calculated. The results are shown in Table 3.
[0357] Ⅱ. The mass contents of Na2O and K2O on the surface of chemically strengthened glass-ceramics were tested. The results are shown in Table 4. At the same time, the two main surfaces of the prepared chemically strengthened glass-ceramics were polished and thinned along the thickness direction using a polishing machine. After the two main surfaces were thinned by 3 μm each, the thinned chemically strengthened glass-ceramics were obtained. The mass percentages of K2O and Na2O on the surface of the thinned chemically strengthened glass-ceramics were tested by XRF. The results are shown in Table 4. The value of relational formula B was calculated. The results are shown in Table 4.
[0358] III. Test the average sandpaper drop resistance height, single rod static pressure strength, Vickers hardness of the chemically strengthened glass-ceramics and the average size of the longest side of 80% of the fragments in two-dimensional vertical projection after the drop test. The results are shown in Table 4.
[0359] Example 2-Example 14
[0360] The above methods are respectively carried out with reference to Example 1, except that the glass composition, glass thickness, different process parameters and corresponding test results of each example are shown in Tables 1 to 4, respectively.
[0361] The DSC curve of the substrate glass of Example 13 is as follows: Figure 1 As shown by Figure 1 It can be seen that the endothermic peak and the exothermic peak of the substrate glass of this embodiment can be used to select the appropriate nucleation temperature and crystallization temperature.
[0362] The XRD pattern of the glass-ceramics of Example 13 is as follows: Figure 2 As shown, the XRD spectrum comparison of the glass-ceramics of Example 13 before and after chemical strengthening is as follows Figure 3 As shown. Figure 2 and Figure 3 It can be seen that in the present application, the main crystalline phase in the glass-ceramics used to prepare chemically strengthened glass-ceramics and the chemically strengthened glass-ceramics is the lithium disilicate crystalline phase, and the crystalline phase structure of the glass-ceramics does not undergo obvious changes before and after the chemical strengthening treatment.
[0363] The transmittance curve of the glass-ceramics of Example 13 is as follows: Figure 4 As shown, the transmittance curve comparison of the microcrystalline glass of Example 13 before and after chemical strengthening is as shown in Figure 5 As shown. Figure 4 and Figure 5 It can be seen that in the present application, the microcrystalline glass and the chemically strengthened microcrystalline glass used to prepare the chemically strengthened microcrystalline glass are both transparent in the visible light range and have high transmittance, and the transmittance of the microcrystalline glass does not change significantly before and after the chemical strengthening treatment.
[0364] The stress-to-thickness curve of the chemically strengthened glass-ceramics of Example 13 is as follows: Figure 6 As shown by Figure 6 It can be seen that the chemically strengthened glass-ceramics has a better stress distribution.
[0365] The stress-to-thickness curves of the chemically strengthened glass-ceramics of Example 2, Example 3, Comparative Example 4 and Comparative Example 5 are shown in FIG. Figure 7 As shown by Figure 7 It can be seen that the chemically strengthened microcrystalline glass needs to meet a specific stress distribution in order to take into account good drop performance and good fragmentation effect after the chemically strengthened microcrystalline glass is broken, so as to ensure better safety performance.
[0366] The vertical projections of the chemically strengthened glass-ceramics of Examples 13 and 14 on the two-dimensional plane after the fragments were broken in the drop test are as follows: Figure 8 and Fig. 9 As shown in the figure, it can be seen that after the chemically strengthened microcrystalline glass is dropped and broken, the fragments produced are relatively large, and a large number of small fragments that are easy to fly around will not be formed, which can avoid safety hazards.
[0367] Comparative Example 1-Comparative Example 12
[0368] The above are respectively carried out with reference to Example 1, except that the glass composition, thickness, different process parameters and corresponding test results of each comparative example are shown in Table 1 to Table 4. Among them, the chemically strengthened microcrystalline glass of Comparative Examples 6 and 12, after being broken in the drop test, the vertical projection of the fragment particles on the two-dimensional plane is as follows: Fig.10 and Fig.11 As shown in the figure, it can be seen that the fragments produced by the chemically strengthened microcrystalline glass after being broken by falling impact are relatively small.
[0369] Expansion softening point test: In order to analyze the 3D hot bending effect of the microcrystalline glass of the present application, the thermal expansion coefficient test curves of the microcrystalline glass in some embodiments were tested, and the expansion softening point was obtained. See Table 2 for details. From the test results, it can be seen that the expansion softening point of the microcrystalline glass of the present application is between 750°C and 820°C, indicating that the microcrystalline glass of the present application is conducive to 3D hot bending molding to prepare 3D curved microcrystalline glass.
[0370]
[0371]
[0372]
[0373]
[0374]
[0375]
[0376]
[0377]
[0378]
[0379]
[0380] It can be seen from the embodiments and comparative examples of the above statements 1 to Table 4 that, compared with the comparative example, the embodiment scheme of the present application is adopted, by making the tensile stress line density value of the chemically strengthened microcrystalline glass whose main crystal phase is the lithium disilicate crystal phase and the ratio of the stress integral of the tensile stress layer near the middle position to the thickness t satisfy a specific difference relationship, while ensuring that the chemically strengthened microcrystalline glass has a higher overall stress level, it can ensure that the internal stress distribution of the chemically strengthened microcrystalline glass is safer, thereby facilitating the chemically strengthened microcrystalline glass to maintain a safe stress state. When the chemically strengthened microcrystalline glass is broken by falling impact, the fragments generated are also relatively large, and a large number of small fragments that are easy to splash around will not be formed, which can avoid safety hazards.
[0381] In the schemes of Comparative Examples 1 to 12, the stress characteristics of the chemically strengthened microcrystalline glass do not meet the specific requirements of the present application, such as the ratio of the tensile stress linear density value and the stress integral of the tensile stress layer near the middle position to the thickness t does not meet the specific difference relationship required by the present application. Finally, the chemically strengthened microcrystalline glass obtained in the schemes of each comparative example either has a poor sandpaper drop height resistance and cannot achieve excellent drop damage resistance, or has a low single-rod static pressure strength that can be tolerated and cannot achieve excellent compression damage resistance, or has a low Vickers hardness, or the fragments produced after the drop impact are small and cannot achieve high safety performance.
[0382] For example, in the above-mentioned comparative examples 4 to 6, 8 to 9 and 12, although a higher depth of the compressive stress layer and a higher tensile stress line density are obtained after chemical strengthening treatment, due to the relatively unreasonable stress distribution of the tensile stress layer, the tensile stress line density value and the ratio of the stress integral of the tensile stress layer near the middle position to the thickness t cannot reach a specific difference relationship. Ultimately, the anti-drop damage performance and fragmentation effect of the chemically strengthened microcrystalline glass obtained in these comparative examples are not as good as the chemically strengthened microcrystalline glass of the embodiment of the present application. In the above-mentioned comparative examples 1 to 3, 10 to 11 and 7, due to the relatively unreasonable stress distribution of the tensile stress layer, the tensile stress line density value and the ratio of the stress integral of the tensile stress layer near the middle position to the thickness t cannot reach a specific difference relationship. Although the fragments are larger after the final breakage, the overall anti-drop damage performance is not as good as the chemically strengthened microcrystalline glass of the embodiment of the present application. For another example, in Comparative Examples 1 to 3, Comparative Example 6, Comparative Example 8 to Comparative Example 9 and Comparative Example 12, since the stress characteristics and surface component contents of the obtained chemically strengthened glass-ceramics do not meet the specific relationship requirements, ultimately, the single-rod static pressure strength that the chemically strengthened glass-ceramics obtained in these comparative examples can withstand is lower than that of the chemically strengthened glass-ceramics in the embodiments of the present application.
[0383] For another example, in Example 3, Examples 12 to 14, Comparative Example 4, and Comparative Example 10 to Comparative Example 12, glass-ceramics having the same glass composition and crystal structure are used to prepare chemically strengthened glass-ceramics. However, due to the difference in the tensile stress linear density value of the prepared chemically strengthened glass-ceramics and the ratio of the stress integral of the tensile stress layer near the middle position to the thickness t, it is finally found that the chemically strengthened glass-ceramics prepared in Example 3 and Examples 12 to 14 that meet the requirements of the technical solution scope of the present application not only have a sandpaper drop height greater than 1.6 m, but also excellent drop damage resistance, and the fragments produced after the drop impact are larger, and the average size of the longest side of the fragment particles under the two-dimensional vertical projection is greater than or equal to 10 mm , with higher safety performance, while the chemically strengthened glass-ceramics prepared in Comparative Examples 4 and 12, which do not meet the requirements of the scope of the technical solution of the present application, not only have a sandpaper drop height of less than 1.6m, but also have smaller fragments after the drop impact and breakage, and the average size of the longest side of the fragment particles under the two-dimensional vertical projection is no more than 5mm. At the same time, the chemically strengthened glass-ceramics prepared in Comparative Examples 10 and 11, which do not meet the requirements of the scope of the technical solution of the present application, although the fragments produced after the drop impact and breakage are larger, the average size of the longest side of the fragment particles under the two-dimensional vertical projection is greater than or equal to 10mm, but the sandpaper drop height does not exceed 1.4m, and the anti-drop damage performance is obviously not as good as the embodiment of the present application. This shows that for glass-ceramics with lithium disilicate as the main crystalline phase, by making the prepared chemically strengthened glass-ceramics meet specific stress characteristics, so that the chemically strengthened glass-ceramics has a specific stress distribution structure, it can not only improve the mechanical strength performance of the chemically strengthened glass-ceramics and improve its damage resistance, but also enable the chemically strengthened glass-ceramics to maintain a safe stress state, and have higher safety performance.
[0384] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened glass-ceramics contains a lithium disilicate crystalline phase, wherein the lithium disilicate crystalline phase has a higher mass percentage than other crystalline phases present in the chemically strengthened glass-ceramics; The chemically strengthened glass-ceramics has a compressive stress layer on the surface and a tensile stress layer inside; The chemically strengthened glass-ceramics satisfies the following relationship: Preferably, A≥50000, more preferably A≥51000, and more preferably, the value of A is 49500 to 65000; Wherein, CT_LD is the tensile stress linear density, in MPa / mm, CT_LD≥60000MPa / mm, t is the thickness of chemically strengthened glass-ceramics, in mm, is the ratio of the stress integral of the tensile stress layer from 2 times DOL_0 from the main surface of the chemically strengthened glass-ceramics to the position half the thickness of the chemically strengthened glass-ceramics along the thickness direction of the chemically strengthened glass-ceramics to the thickness t, in units of MPa / mm, where x is the depth from the main surface of the chemically strengthened glass-ceramics, In equation A, data is substituted into the calculation according to the above unit requirements to obtain the calculation result. The unit does not participate in the calculation.
2. The chemically strengthened glass-ceramics according to claim 1, characterized in that: The chemically strengthened glass-ceramics satisfies the following relationship: B=[|CT_AV|×(t / 2-DOL_0)]×[5×M K2O / (5×M K2O +0.5×M Na2O )],B≥9000 MPa·μm, preferably, B ≥ 9100 MPa·μm, more preferably, B ≥ 9200 MPa·μm, more preferably, the value of B is 9000 MPa·μm to 13000 MPa·μm; Where |CT_AV| is the absolute value of the average tensile stress, t is the thickness of chemically strengthened glass-ceramics, M K2O is the mass percentage of K2O on the surface of chemically strengthened glass-ceramics, M Na2O is the mass percentage of Na2O on the surface of chemically strengthened glass-ceramics.
3. The chemically strengthened glass-ceramics according to claim 1 or 2, characterized in that: The chemically strengthened microcrystalline glass satisfies the following relationship: C=CS_50 / |CT_CV|, C≥0.85, preferably 0.85-1.5, more preferably 0.9-1.3, more preferably 0.9-1.2; wherein CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened microcrystalline glass, in MPa, and |CT_CV| is the absolute value of the maximum tensile stress, in MPa.
4. The chemically strengthened glass-ceramics according to any one of claims 1 to 3, characterized in that: The chemically strengthened glass-ceramics meets the following requirements: 140.00 MPa≤CS_50, preferably, 180.00 MPa≤CS_50, more preferably, 180.00 MPa≤CS_50≤240.00 MPa, wherein CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened microcrystalline glass; and / or, 90.00 μm≤DOL_0, preferably, 100.00 μm≤DOL_0, more preferably, 100.00 μm≤DOL_0≤160.00 μm, wherein DOL_0 is the depth of the compressive stress layer; and / or, 0.18≤DOL_0 / t, preferably, 0.20≤DOL_0 / t≤0.25, more preferably, 0.22≤DOL_0 / t≤0.23, wherein DOL_0 is the depth of the compressive stress layer, and t is the thickness of the chemically strengthened glass-ceramics; and / or, 150MPa≤|CT_CV|, preferably, 150MPa≤|CT_CV|≤250MPa, more preferably, 180MPa≤|CT_CV|≤250MPa, wherein |CT_CV| is the absolute value of the maximum tensile stress; and / or, 100.00 MPa≤|CT_AV|, preferably, 100.00 MPa≤|CT_AV|≤160.00 MPa, more preferably, 130.00 MPa≤|CT_AV|≤160.00 MPa, wherein |CT_AV| is the absolute value of the average tensile stress; and / or, 65000.00MPa / mm≤CT_LD≤90000.00MPa / mm, more preferably, 70000.00MPa / mm≤CT_LD≤90000.00MPa / mm, wherein CT_LD refers to tensile stress linear density; and / or, M K2O ≤3.0%, preferably 0.2% to 2%, more preferably 0.3% to 1.6%, wherein M K2O is the mass percentage of K2O on the surface of chemically strengthened glass-ceramics; and / or, M Na2O ≥5.0%, preferably 5.0% to 20%, more preferably 6% to 17%, wherein M Na2O is the mass percentage of Na2O on the surface of chemically strengthened glass-ceramics.
5. The chemically strengthened glass-ceramics according to any one of claims 1 to 4, characterized in that: After the two main surfaces of the chemically strengthened microcrystalline glass are thinned by 3 μm, the chemical microcrystalline glass obtained satisfies: the mass percentage M' of K2O on the surface of the chemical microcrystalline glass K2O and the mass percentage of Na2O on the surface of chemical glass-ceramics M' Na2O for: M' K2O <3.0%, preferably 0.0% to 1%, more preferably 0.1% to 0.5%, M' Na2O <15.0%, preferably 3.0% to 14%, more preferably 4% to 12%.
6. The chemically strengthened glass-ceramics according to any one of claims 1 to 5, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in molar percentage of oxides, comprises: SiO2: 58% to 66%, Al2O3: 0% to 3.5%, P2O5: 1% to 2.5%, ZrO2: 3.5% to 5.5%, Li2O: 22% to 32%, SrO: 0% to 2.5%, Na2O: 0% to 3%.
7. The chemically strengthened glass-ceramics according to claim 6, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in molar percentage of oxides, further comprises: K2O: 0% to 1%, CaO: 0% to 1.5%, B2O3: 0% to 1%, Ta2O5: 0% to 1%, BaO: 0% to 2.5%.
8. The chemically strengthened glass-ceramics according to claim 6 or 7, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in molar percentage of oxides, comprises: The molar percentage of SiO2 is 60% to 65%, preferably 60.5% to 64.5%; and / or, The molar percentage of Al2O3 is 1% to 3.5%, preferably 1% to 2.5%, more preferably 1% to 1.5%; and / or, The molar percentage of P2O5 is 1% to 2%, preferably 1.2% to 2%; and / or, The molar percentage of ZrO2 is 4% to 5%, preferably 4.2% to 5%; and / or, The molar percentage of Li2O is 23% to 31%, preferably 24% to 30%, more preferably 27% to 30%; and / or, The molar percentage of SrO is 0% to 2%, preferably 0% to 1.9%; and / or, The molar percentage of Na2O is 0% to 2.6%, preferably 0% to 1%; and / or, The molar percentage of K2O is 0% to 0.7%, preferably 0% to 0.5%; and / or, The molar percentage of CaO is 0% to 1%, preferably 0% to 0.95%; and / or, The molar percentage of B2O3 is 0% to 0.7%, preferably 0% to 0.5%; and / or, The molar percentage of Ta2O5 is 0% to 0.7%, preferably 0% to 0.5%; and / or, The molar percentage of BaO is 0% to 2%, preferably 0% to 1.9%.
9. The chemically strengthened glass-ceramics according to any one of claims 1 to 8, characterized in that: The chemically strengthened glass-ceramics meets the following requirements: 2.00≤n(SiO2) / n(Li2O)≤2.40, preferably, 2.00≤n(SiO2) / n(Li2O)≤2.30, more preferably, 2.02≤n(SiO2) / n(Li2O)≤2.20; and / or, 90%≤n(SiO2)+n(Li2O)≤95%, preferably, 90%≤n(SiO2)+n(Li2O)≤92%; wherein n(SiO2) is the molar percentage content of SiO2 at the center of the chemically strengthened glass-ceramics, and n(Li2O) is the molar percentage content of Li2O at the center of the chemically strengthened glass-ceramics.
10. The chemically strengthened glass-ceramics according to any one of claims 1 to 5, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in percentage by mass of oxides, comprises: SiO2: 60% to 70%, Al2O3: 0% to 6%, P2O5: 2% to 8%, ZrO2: 8% to 12%, Li2O: 10% to 20%, SrO: 0% to 6%, Na2O: 0% to 3%.
11. The chemically strengthened glass-ceramics according to claim 10, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in percentage by mass of oxides, further comprises: K2O: 0% to 2%, CaO: 0% to 2%, B2O3: 0% to 1%, Ta2O5: 0% to 2%, BaO: 0% to 6%.
12. The chemically strengthened glass-ceramics according to claim 10 or 11, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in percentage by mass of oxides, comprises: The mass percentage of SiO2 is 62% to 68%, preferably 63% to 67%; and / or, The mass percentage of Al2O3 is 1% to 6%, preferably 2% to 6%, more preferably 2% to 3%; and / or, The mass percentage of P2O5 is 3% to 6%, preferably 3% to 5%, more preferably 4% to 5%; and / or, The mass percentage of ZrO2 is 8% to 11%, preferably 9% to 11%; and / or, The mass percentage of Li2O is 11% to 18%, preferably 12% to 16%, more preferably 14% to 16%; and / or, The mass percentage of SrO is 0% to 5%, preferably 0% to 4%; and / or, The mass percentage of Na2O is 0% to 2.8%, preferably 0% to 1%; and / or, The mass percentage of K2O is 0% to 1.5%, preferably 0% to 1.2%; and / or, The mass percentage of CaO is 0% to 1%, preferably 0% to 0.95%; and / or, The mass percentage of B2O3 is 0% to 0.8%, preferably 0% to 0.6%; and / or, The mass percentage of Ta2O5 is 0% to 1.8%, preferably 0% to 1.5%; and / or, The mass percentage of BaO is 0% to 5.5%, preferably 0% to 5%.
13. The chemically strengthened glass-ceramics according to any one of claims 1 to 12, characterized in that: The crystallinity of the chemically strengthened glass-ceramics is not less than 60%, preferably, the crystallinity of the chemically strengthened glass-ceramics is 70% to 90%, more preferably, the crystallinity of the chemically strengthened glass-ceramics is 70% to 80%; and / or, In the chemically strengthened glass-ceramics, the average grain size does not exceed 50 nm, preferably, the average grain size is 10 nm to 40 nm, and more preferably, the average grain size is 15 nm to 30 nm; and / or, In the chemically strengthened glass-ceramics, the mass of lithium disilicate crystal phase accounts for 80wt% to 100wt% of all crystal phases; and / or, The mass percentage of the petalite crystalline phase in the chemically strengthened glass-ceramics is less than or equal to 10%, preferably less than or equal to 5%, and more preferably, does not contain the petalite crystalline phase.
14. The chemically strengthened glass-ceramics according to any one of claims 1 to 13, characterized in that: When the thickness does not exceed 0.70 mm, the b value of the chemically strengthened glass-ceramics is less than 1.0, preferably, the b value is less than 0.8, and more preferably, the b value is ≤ 0.6; and / or The chemically strengthened glass-ceramics is transparent in the visible light wavelength range. Preferably, for light with a wavelength of 550 nm, the transmittance of the chemically strengthened glass-ceramics is ≥85%, preferably, the transmittance is ≥90%, and more preferably, the transmittance is ≥90.2%.
15. The chemically strengthened glass-ceramics according to any one of claims 1 to 14, characterized in that: The Young's modulus of the chemically strengthened glass-ceramics is not less than 100 GPa, preferably, the Young's modulus is not less than 110 GPa, and more preferably, the Young's modulus is 110 GPa to 130 GPa; and / or, The density of the chemically strengthened glass-ceramics is not less than 2.54 g / cm 3 , preferably, the density is 2.54 g / cm 3 ~2.64g / cm 3 and / or, The refractive index of the chemically strengthened glass-ceramics is ≤1.60, preferably, the refractive index is 1.55 to 1.60; and / or, The Vickers hardness of the chemically strengthened glass-ceramics is ≥700kgf / mm 2 , preferably, the Vickers hardness is 700kgf / mm 2 ~850kgf / mm 2 .
16. The chemically strengthened glass-ceramics according to any one of claims 1 to 15, characterized in that: The thickness t of the chemically strengthened glass-ceramics is 0.35 mm to 1.0 mm, preferably, the thickness t is 0.4 mm to 0.7 mm, and more preferably, the thickness t is 0.45 mm to 0.55 mm; and / or, the chemically strengthened glass-ceramics is 2D, 2.5D, 3D or special-shaped; and / or, the chemically strengthened glass-ceramics is of equal thickness or unequal thickness.
17. The chemically strengthened glass-ceramics according to any one of claims 1 to 16, characterized in that: The chemically strengthened glass-ceramics is subjected to a sandpaper drop resistance test, and the sandpaper used is 80-mesh sandpaper. When the thickness does not exceed 0.70 mm, preferably when the thickness is 0.4 mm to 0.7 mm, and more preferably when the thickness is 0.45 mm to 0.55 mm, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.60 m, and preferably, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is 1.65 m to 2.50 m; and / or, The chemically strengthened glass-ceramics are squeezed by a 10 mm diameter round-headed metal pressure rod to test the single-rod static pressure strength that the chemically strengthened glass-ceramics can withstand. The average value of the single-rod static pressure strength that the chemically strengthened glass-ceramics can withstand is greater than 200N, preferably greater than 230N.
18. The chemically strengthened glass-ceramics according to claim 3, characterized in that: The chemically strengthened glass-ceramics meets the following requirements: The value of relational formula A is: 54802.89, 51024.81, 57170.35, 52689.22, 52272.54, 58526.63, 54807.04, 56429.32, 52815.28, 53580.63, 54032.42, 54060.10, 53361.40 or 54841.31; and / or, The value of relational formula B is: 10333.74 MPa·μm, 11642.77 MPa·μm, 11864.03 MPa·μm, 10818.69 MPa·μm, 10199.45 MPa·μm, 10638.55 MPa·μm, 10862.45 MPa·μm, 9442.20 MPa·μm, 9292.34 MPa·μm, 10157.90 MPa·μm, 10637.99 MPa·μm, 10907.18 MPa·μm, 10429.05 MPa·μm or 11586.62 MPa·μm; and / or, The values of relational formula C are: 0.93, 1.12, 1.00, 0.97, 1.03, 0.99, 1.01, 0.98, 0.92, 1.05 or 1.
06.
19. A cover glass, characterized in that: The cover glass comprises the chemically strengthened glass-ceramic according to any one of claims 1 to 18.
20. An electronic device, characterized in that: The electronic device comprises the chemically strengthened glass-ceramic according to any one of claims 1 to 18.
21. The electronic device according to claim 20, characterized in that: The electronic device includes a housing assembled on the outside of the electronic device, and the housing includes the chemically strengthened micro-ceramic glass according to any one of claims 1 to 18.
22. The electronic device according to claim 21, characterized in that: The housing includes a display cover assembled on the front side of the electronic device, and the display cover includes the chemically strengthened microcrystalline glass according to any one of claims 1 to 18.
23. The electronic device according to claim 21 or 22, characterized in that: The housing includes a back cover assembled on the back side of the electronic device, and the back cover includes the chemically strengthened micro-ceramic glass according to any one of claims 1 to 18.
24. The electronic device according to any one of claims 21 to 23, characterized in that: The electronic device also includes a camera assembly located inside the housing, the housing includes a camera protection cover, the camera protection cover is covered on the camera assembly, and the camera protection cover includes the chemically strengthened microcrystalline glass according to any one of claims 1-18.
25. The electronic device according to any one of claims 21 to 24, characterized in that: The electronic device further includes a middle frame, and the middle frame includes the chemically strengthened microcrystalline glass according to any one of claims 1 to 18.
26. A glass device, characterized in that: The glass device comprises the chemically strengthened glass-ceramic according to any one of claims 1 to 18.
Citation Information
Patent Citations
Microcrystalline glass and chemically strengthened microcrystalline glass
CN112645600A
Glass ceramic with ultrahigh bifurcation threshold value
CN113929308A
Glass ceramic, chemically strengthened glass ceramic, cover plate glass and electronic equipment
CN118290031A
Chemically strengthened microcrystalline glass, cover plate glass, electronic equipment and glass device
CN118702411A
Cited By
Glass ceramic, preparation method thereof, electronic equipment cover plate prepared from glass ceramic and electronic equipment cover plate assembly
CN120736800A
Chemically strengthened microcrystalline glass, cover glass, electronic device, and glass device
WO2026067725A1